Jacques Thobie. 22 avril 1929 - 8 avril 2020 - Saul, Samir (Revue française d'histoire économique, 2020)
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0

La France et l'Égypte de 1882 à 1914 : Intérêts économiques et implications politiques - Saul, Samir (Institut de la gestion publique et du développement économique, Comité pour l’histoire économique et financière de la France, 1997)
Section: xix, 787 pages ; 22 cm
Keywords: Banque de Paris et des Pays-Bas; Crédit lyonnais; Egipto; Egypt; Société générale; canal de Suez; histoire économique et financière; relations franco-britanniques; Égypte

Bankrupt parisian minor banks and petty bankers from 1882 to 1911 - Saul, Samir (Revue française d'histoire économique, 2020)
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0

Découpage colonial et nation-building en Syrie mandataire : regards français sur les suites de l’accord Sykes-Picot (1916-1938) - Saul, Samir (Guerres mondiales et conflits contemporains, 2015)
L’accord Sykes-Picot est souvent évoqué dans le contexte de la guerre qui se déroule en Syrie depuis 2011. Multiconfessionnel, le pays est menacé d’un éclatement qui remettrait en question les frontières tracées par l’accord Sykes-Picot. Quant au projet américain d’un « Grand Moyen Orient », il redécouperait la région sur des bases confessionnelles. L’irruption d’éléments djihadistes au nord de l’Irak au lendemain de la rédaction du présent article souligne la réalité des défis posés aux États de la région. La Syrie mandataire est une entité multiconfessionnelle et multiethnique qui évolue vers la formation nationale. Mais elle est gouvernée selon des critères confessionnels et ethniques. L’article se penche sur la dynamique contradictoire de la politique française qui se traduit par l’inclusion formelle d’autant d’habitants que possible dans l’État syrien, mais aussi par sa segmentation sur des bases communautaires et confessionnelles. Plutôt qu’à l’action officielle de la France, il s’intéresse au regard porté par la presse française sur cette corrélation problématique.
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0

La fabrique de l’ennemi civilisationnel - Saul, Samir (Relations, 2015)
Un article de la revue Relations, diffusée par la plateforme Érudit.

Introduction - Saul, Samir (Guerres mondiales et conflits contemporains, 2016)
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0

Réforme constitutionnelle avortée en France - Saul, Samir (Relations, 2016)
Un article de la revue Relations, diffusée par la plateforme Érudit.

La Turquie entre l’impasse et l’inconnu - Saul, Samir (Relations, 2016)
Un article de la revue Relations, diffusée par la plateforme Érudit.

Le contexte et la contexture : évolution historique et cadre structurel - Saul, Samir (La France et l'Égypte de 1882 à 1914 : Intérêts économiques et implications politiques, 1997)
Code: La France et l'Égypte de 1882 à 1914 : Intérêts économiques et implications politiques

Les agences du Crédit lyonnais en Egypte : l’insertion d’une banque de dépôts dans une économie d’Outre-Mer (1875-1956) - Saul, Samir (Le Crédit lyonnais (1863-1986), 2003)
Section: Économie

Les pouvoirs publics métropolitains face à la Dépression: La Conférence économique de la France métropolitaine et d’Outre-Mer (1934–1935) - Saul, Samir (French Colonial History, 2011)
With the Depression eroding France’s foreign trade, government authorities felt compelled to convene an imperial conference in order to seek solutions based on the consolidation of economic ties with the Empire, Inspiration came partly from the conference held in Ottawa in 1932 by Great Britain and its Dominions. The aim of the Paris gathering was to promote increased exports to the colonies as a substitute to foreign markets lost during the downswing. Likewise, importers were encouraged to buy from the colonies, rather than from foreign countries, thereby raising the purchasing power of the colonial population and its ability to import French goods. Although the program to institute a coordinated imperial economy appeared logical in principle, its implementation was complicated by economic realities and the non-complementary character of the metropolitan and the colonial economies.

La COFACE : des opérations avec garantie de l'État au risque pays - Saul, Samir (Les cahiers Irice, 2010)

Milieux d'affaires de l'Outre-Mer français et Grande Dépression des années 1930 - Saul, Samir (French Colonial History, 2009)
Faced with the collapse of international trade and the price of commodities as a result of the Depression, the chambers of commerce of French overseas territories met on four occasions during the 1930s to air their concerns and address requests to authorities. Their congresses provide an ideal and little-known vantage point to observe the stresses and strains of the imperial economy in troubled times. Colonial interests did not necessarily coincide with those of the mother country. The tightening of protectionism in response to the economic crisis was primarily a way of relieving metropolitan interests, sometimes at the expense of overseas French producers and merchants. Two categories of demands emerge from the congresses. The first aimed to reinforce the imperial relationship in order to assist colonial exporters, while the second implicitly questioned the very foundations of an imperial economy, a surprising anticipation of post-1945 developments.

Masterly Inactivity as Brinkmanship: The Iraq Petroleum Company's Route to Nationalization, 1958–1972 - Saul, Samir (The International History Review, 2007)
_eprint: https://doi.org/10.1080/07075332.2007.9641140

L’Histoire des relations internationales: contexte, cheminement et perspectives - Saul, Samir (Penser l'international, 2007)
Chapitre 1 L’Histoire Des Relations Internationales: Contexte, Cheminement Et Perspectives was published in Penser l'international on page 15.
Section: Penser l'international

Politique nationale du pétrole, sociétés nationales et « pétrole franc » - Saul, Samir (Revue historique, 2006)

Regards officiels canadiens sur la politique étrangère de la France gaullienne, 1963-1969 - Saul, Samir (Guerres mondiales et conflits contemporains, 2006)
Les politiques étrangères du Canada et de la France ont peu de similitudes durant les années 1960. L’approche multilatérale, « intégrationniste » et supranationale canadienne et celle fondée sur la primauté des relations bilatérales, du fait national et de l’État-nation, que promeut de Gaulle, sont foncièrement discordantes. L’écart qui sépare les deux pays rend d’autant plus significatif le regard que le Canada officiel porte sur une politique étrangère aussi différente de la sienne. Les milieux officiels canadiens sont bien renseignés sur les fondements et la substance de la politique étrangère de la France gaullienne. Leur attitude est dépassionnée, souvent compréhensive, à son égard. Malgré les dissonances, le Canada doit avoir des rapports convenables avec la France car celle-ci est devenue un sujet de politique …

Roger Le Tourneau : un historien de l'Afrique du Nord face à la décolonisation - Saul, Samir (Outre-Mers. Revue d'histoire, 2006)
Historien de l'Afrique du Nord précontemporaine, Roger Le Tourneau évolue dans un monde professionnel éloigné de l'actualité. Pourtant, il est sollicité par la décolonisation du Maghreb et se prononce sur le bouleversement en cours. Sa position est celle d'un réformiste modéré, conscient de la nécessité de dépasser le cadre colonial traditionnel, sans être acquis à l'idée d'une rupture entre la France et ses possessions. Au fur et à mesure que s'exacerbe le conflit, l'espace du réformateur se rétrécit. Le départ de Le Tourneau de l'Algérie est symbolique de l'effacement des solutions pacifiques. Comprendre l'interprétation que fait l'historien des événements qui se déroulent sous ses yeux constitue l'objet de l'étude. Le parcours de Le Tourneau est instructif à un double titre : d'abord parce qu'il éclaire sur une sensibilité fatalement marginalisée dans l'affrontement ; ensuite parce qu'il permet de saisir sur le vif comment l'historien s'appuie sur son savoir et son sens du mouvement historique pour comprendre le présent à la lumière du passé.

La Banque de Syrie et du Liban (1919-1970): banque française en Méditerranée orientale - Saul, Samir (Entreprises et histoire, 2002)
L’on oublie souvent qu’il existe aussi des contrats de concession de nature financière : tel fut le cas de la Banque de Syrie et du Liban (1919-1970), point d’appui des intérêts économiques français dans ces deux pays. Née de l’intention de la Banque ottomane de préserver sa présence régionale, elle traduit aussi la volonté des pouvoirs publics français de disposer d’une monnaie nouvelle lors de la prise en charge des mandats de la SDN. Levier d’un grand dessein de pénétration et de développement économiques régionaux, la BSL a largement échoué dans ses objectifs. En revanche, elle s’est révélée une affaire exceptionnellement bénéficiaire pour ses actionnaires.

L'état et l'assurance des risques à l'exportation: la COFACE (1946-1966) - Saul, Samir (Histoire, Économie et Société, 2002)
L'assurance-crédit à l'exportation constitue un type particulier d'assurance, lié à l'État et à sa politique commerciale. L'une des principales sociétés d'assurance des risques à l'exportation, la COFACE, n'a pas fait l'objet d'études à caractère historique. Le présent article, portant sur ses deux premières décennies d'activité, est un essai dans ce sens. L'examen des rapports COFACE-État et des mécanismes de l'assurance-crédit à l'exportation conduit à une évaluation chiffrée des résultats de l'action de la COFACE pendant les vingt premières années de son existence. En vue de mettre ces résultats en perspective, la COFACE est confrontée à son équivalent canadien, la SACE. L'article ouvre la voie à de nouvelles études comparatives et historiques des plus importantes sociétés d'assurance des risques à l'exportation. Export credit insurance represents a specific type of insurance, connected to the state and its commercial policy. France's COFACE, one of the major firms specializing in the insurance of export credit risk, has not been studied from a historical standpoint. This article attempts such a study by focusing on its first two decades of activity. Starting with an overview of the COFACE's relations with the state, it examines export credit insurance techniques and concludes with various measurements of the company's performance during the initial twenty years of its existence. In order to put these results in perspective, the COFACE is examined alongside its Canadian counterpart, the Export Credits Insurance Corporation. This article opens the way to further comparative and historical research into the role of the leading export credit insurance companies.

Articuler un pan de la modernité : Pierre Mendès France et les pays du Sud - Saul, Samir (Matériaux pour l'histoire de notre temps, 2001)

La France et la crise du Golfe 1990-1991 : analyse politico-économique d'un virage - Saul, Samir (Études internationales, 1995)
The article situates official French policy during the crisis in the general framework of its international relations. It was somewhat surprising to see a country close to Iraq join the coalition. The first part is a reminder that France was, after the United States, the most zealous of the coalition members, and that its stated objectives did not correspond to its real aims. The second part takes stock of Franco-Iraqi relations in order to assess their state in August 1990. Business dwindled after the 1970s and stagnation set in as a result of the war against Iran and the downturn in oil prices. On the eve of the crisis, relations were at a standstill while accords to settle arrears in payments went into effect. The third part puts Franco-Iraqi relations in the context of the general reorientation of the French economy. At the time of the Gulf crisis, France was turning the page on the era of megaprojects in developing countries and integrating more thoroughly in the developed economies. The article concludes that French policy during the crisis, a short-term political event, was in accord with economic changes occurring over the intermediate term, without being their direct consequence.

Bienveillance et méprise: les réactions françaises au coup de force britannique du 4 février 1942 en Égypte - Saul, Samir (Guerres mondiales et conflits contemporains, 1994)
Le 6 février 1942, l'armée britannique cerne le palais royal au Caire et l'ambassadeur Lampson oblige le roi Faruq à désigner un gouvernement composé exclusivement de membres du parti Wafd. Violation brutale de l'indépendance du pays, reconnue par l'Angleterre en 1922, cette action laisse une marque profonde sur l'histoire contemporaine de l'Egypte. Il est un aspect de cette affaire qui est resté dans l'ombre, à savoir l'attitude de ceux que l'Egypte ne laisse jamais indifférents: les Français. L'occasion leur est donnée de rappeler aux Anglais le principe du respect de la souveraineté et de l'indépendance d'autrui, avec d'autant plus d'ardeur que la leçon leur a été assenée en 1941 au sujet de la Syrie et du Liban. Or, les réactions françaises surprennent: silence du côté de la France libre; incompréhension à Vichy et en France occupée. On February 6, 1942, while the British army surrounded the royal palace in Cairo, Lampson, the ambassador, compelled King Faruq to name a cabinet made up solely of Wafd Party members. The brutal violation of the country's independence, recognized by Britain in 1922, left a profound imprint on contemporary Egyptian history. One aspect of this event remains unknown, namely the reaction of the French, a party never indifferent to Egypt. It had the opportunity to remind the British of the principle of respect for the sovereignty and independence of others, all the more forcefully because it had been lectured in 1941 about the rights of Syria and Lebanon. Yet, French reactions are surprising. While Free France remained silent, Vichy and occupied France seemed uncomprehending.

Y a-t-il une question des minorités en Égypte? Analyses égyptiennes et contexte historique - Saul, Samir (Guerres mondiales et conflits contemporains, 1988)

Conjonctures, adaptation et croissance: le Crédit foncier franco-canadien (1880-1979) - Saul, Samir (Histoire, Économie et Société, 1986)

L'impérialisme, passé et présent: un essai - Saul, Samir (Les Indes savantes, 2023)
Impérialisme. Très usité jusqu'aux années 1970, le vocable se rencontre moins souvent depuis. L'actualité incite à le revisiter, autant comme concept que comme phénomène historique. L'accélération de l'intégration de l'économie mondiale, les mutations qu'elle traverse, l'unipolarité géopolitique et sa contestation, enfin les heurts internationaux, obligent à chercher des cadres d'intelligibilité en renouant avec un concept fécond. Ce livre est une synthèse mettant en dialogue la théorie et l'histoire afin de fournir un panorama explicatif des formes prises par l'impérialisme. Abordant l'impérialisme par une approche historienne, il tient de la fresque historique et de la démarche théorique. Il établit une typologie des régimes liant les économies nationales et les régimes de contrôle impérialiste. L'ouvrage innove par l'effort de dégager l'unicité du phénomène, tout en l'ancrant dans la spécificité des conditions dans lesquelles il s'inscrit. Il met l'accent sur la relation impérialiste et sa conceptualisation au cours des périodes moderne, contemporaine et actuelle. Il se démarque par la démonstration que l'impérialisme, n'appartenant pas au seul passé, est toujours de notre temps. Il atteint aujourd'hui une forme plus prégnante, prend une extension plus large et repose sur des mécanismes originaux.

Intérêts économiques français et décolonisation de l'Afrique du Nord (1945-1962) - Saul, Samir (Librairie Droz, 2016)
Ce livre engage une enquête approfondie sur l'activité économique française en Afrique du Nord à la veille de la décolonisation. Mettant à contribution un vaste ensemble de fonds publics, de papiers privés et d'archives du monde des affaires, il participe de l'histoire des relations internationales, de l'histoire coloniale/d'outre-mer et de l'histoire des entreprises. Vérifier l'existence d'une relation entre les intérêts économiques français et l'accession à l'indépendance du Maghreb est au cœur de la démarche. Il s'agit de déterminer si l'Afrique du Nord avait cessé d'être rentable, et si les milieux d'affaires et l'Etat métropolitain s'en étaient départis pour des motifs économiques. L'enquête conduit au constat que l'économie nord-africaine demeure attractive et que les intérêts économiques français ne favorisent pas la décolonisation. Ni les milieux d'affaires ni les pouvoirs publics n'obéissent à une logique d'élagage. Les implications de cette conclusion sont de deux ordres : d'abord, le capitalisme n'est pas décolonisateur, nonobstant une tendance récente à croire le contraire ; ensuite, les mouvements nationalistes maghrébins conservent leur centralité comme vecteurs de la décolonisation
Section: 1 vol. (763 p.) : couv.ill en coul. ; 24 cm.

Setting Up a French Military-Industrial Complex in Algeria (1945-1959) - Saul, Samir (The Maghreb Review, 2019)

Recent trends in French historiography on electricity - Saul, Samir (2007 IEEE Conference on the History of Electric Power, 2007)
Beginning practically from scratch about a quarter century ago, a vast storehouse of knowledge has been collected on the history of electricity in France and elsewhere. Caron described the publications by the AHEF as a sort of database. We know a lot more about production and consumption, about companies and people active in the electrical sector, about economic results and social effects, about the legal framework and the political context, about the cultural and artistic aspects of the novelty that was electricity. A large number of historians and graduate students have worked on many fronts. None can be said to have been neglected. That was the predominant trend. Recent historiography tried to embrace all of the history of electricity. To a large extent, it succeeded. What remains to be done ? Three suggestions can be advanced. First, more attention has to be paid to the very recent history of electrification. As time passes and EDF archives become available, more work based on sources will be done on the immediate past. Second, the international dimension has to be strengthened, in two respects. On the one hand, comparisons between France and other countries need to be encouraged. On the other, connections between national electrical systems remain hazy and require clarification and understanding. Third, greater use has to be made of the interdisciplinary approach, electricity being a subject at the crossroads, at the very least, of science, technology, economics, politics, sociology, literature, art and, of course, history.
Keywords: Banking; Books; Companies; Conferences; Cultural differences; History; Industrial economics; Power generation economics; Production; Rail transportation

Has Financial Internationalization Turned into Financial Globalization - Saul, Samir (McMaster University Globalization Working Papers, 2006)

Les usages politiques du passé - Saul, Samir (Relations internationales, 2005)
La mise à contribution du passé dans les projets, débats ou luttes politiques est une pratique courante et ancienne. De fait, l'absence de références au passé aurait de quoi surprendre dans la mesure où les Htiges et différends du présent plongent leurs racines dans un passé immédiat ou lointain. Du coup, l'interprétation du passé devient elle-même à la fois projet et enjeu du présent. Se succédant, les grands mouvements de l'histoire superposent leurs marques sur les configurations inachevées et en cours de mutation. Qu'advienne l'étiage d'un mouvement, que prenne fin une ère, et réapparaissent les contradictions non résolues, les versions divergentes et les visions discordantes. L'instrumentalisation du passé aux fins d'emploi au présent, la vague mémorielle, le «devoir» de mémoire et la construction de son contenu sont plus que jamais des activités de la toute première importance.

La bonne foi dans la conduite internationale des États - Saul, Samir (Relations internationales, 2004)

La Banque d’État du Maroc et la monnaie sous le protectorat - Saul, Samir (La France et l'outre-mer. Un siècle de relations monétaires et financières: colloque tenu à Bercy les 13, 14 et 15 novembre 1996, 1998)

L'intervention anglaise en Égypte et ses fondements, 1875-1882 - Saul, Samir (Université de Montréal, 1977)
Keywords: Diplomatic relations; Economic history; International economic relations

Far from the Light of Day: Bankrupt Parisian Minor Banks and Petty Bankers from 1882 to 1911 - Saul, Samir (Revue française d'histoire économique, 2020)
Number: 2

Les intérêts économiques français se détournaient-ils de l'Afrique du Nord à la veille des indépendances? - Saul, Samir (IBLA Revue de l'Institut des belles-lettres arabes, 2020)
Number: 226

Huit cents ans de faillites d'État - Saul, Samir (L'Histoire, 2011)
Le feuilleton de la faillite de l'État grec nous tient en haleine depuis plusieurs mois. Le défaut de paiement des États, à vrai dire, n'est pas chose nouvelle. Samir Saul nous explique pourquoi ils se sont même multipliés depuis le XIXe siècle. Pourquoi aussi aujourd'hui ils sont plus dangereux que jamais.

Imperialism: As Rampant Today As in the Past - Saul, Samir (Baraka Books, 2025)
2024 is not 1914. Nonetheless, imperialism was the dominant system then, as it is now. A century ago, several neo-mercantilist imperial powers vied to establish primacy over the others. Things have changed. Our era is one of planetary imperialism and globalized capitalism where one power, the U.S., already exercises hegemony over all. No other, including China and Russia, has the need or the capacity to replace it. We are not faced with relatively equal adversaries facing off, as in WW1, but with one hegemonic power trying desperately, by and all means, to cling to its world-wide domination. Herein lies the source of the major tensions and conflicts in the world today. Samir Saul revisits the notion of imperialism, establishes a typology of imperialisms and shows how relevant the concept is today. Since the fall of the Soviet Bloc, the term ?imperialism? has largely disappeared from public discourse, even among left-wing or formerly left-wing authors and publications. Yet reality is relentless, and the issue has returned in full force. This book attempts to develop a new interpretation of imperialism, based on a historical approach. Highlighting the historical continuity of imperialism, it shows how crucial it is to understanding what is happening today.
OCLC: 1493065208

In memoriam. Jacques Thobie (1929-2020) - Metzger, Chantal; Saul, Samir (Guerres mondiales et conflits contemporains, 2020)
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0

Entreprises, production et marchés. Entreprises, Sous forme d’un entretien entre Dominique Barjot, Samir Saul. Table ronde tenue le 21 septembre 2012 dans le cadre du congrès annuel du Comité Français des Sciences historiques, Bibliothèque Carnegie, 2, Place Carnegie Reims - Barjot, Dominique; Saul, Samir (Revue française d'histoire économique, 2014)
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0

De mémoire et d’histoire - Sollai, Luca; Saul, Samir (Cahiers d'histoire, 2022)
Number: 2 Volume 38, numéro 2, automne 2022 De mémoire et d’histoire Sous la direction de Luca Sollai et Samir Saul
Keywords: =CL

Alfred Naquet et le radicalisme avant l'avènement de la République radicale (1832-1891) - Fima, Joseph (Université de Montréal, 1999)
Keywords: 1834-1916; =CL; Alfred; Naquet

ELF-ERAP et le Congo: les vicissitudes d’un mariage de raison (1968-1978) - Malonga, Ferdinand; Saul, Samir (Histoire, économie & société, 2010)
Cet article se propose d’expliquer les origines et l’évolution de l’association, à première vue contre-nature, entre un État se proclamant du marxisme et une société étrangère issue de l’ex-métropole. C’est dans un contexte politique et économique bien trouble qu’ELF-ERAP décide de relancer ses activités pétrolières au Congo. L’article essaie de repérer la stratégie adoptée par ELF-ERAP face à un interlocuteur exigeant qui tente d’appliquer les méthodes des pays de l’Est. Quoique tendue et instable, une coopération s’instaure entre ces deux partenaires qui ne semblent pas complémentaires.

Le projet d'Eurafrique en France (1946-1960) : quête de puissance ou atavisme colonial ? - Dramé, Papa; Saul, Samir (Guerres mondiales et conflits contemporains, 2004)

Origines et circonstances immédiates du partage du Cameroun entre la France et l'Angleterre pendant la première guerre mondiale - Eyelom, Franklin (Université de Montréal, 1997)

Le conflit mondial du XXIe siècle - Seymour, Michel; Saul, Samir (L'Harmattan, 2025)
Les heurts internationaux se multiplient et l’affrontement armé entre grandes puissances pointe à l’horizon. Le discours belliqueux entretient une ambiance belligène. Tandis que l’« ordre » américain se délite, les États-Unis se débattent comme une bête blessée pour le rétablir et empêcher l’avènement d’une ère post-étasunienne. C’est le reste du monde qui fait les frais de cette crise hégémonique de l’impérialisme américain. Autant le besoin de comprendre est lancinant, autant l’offre se réduit à un matraquage de « récits » et de « narratifs » déformants, à une pensée unique mensongère et infantilisante. La fiction se substitue au réel. Contre la propagande et la désinformation, ce livre réunit des articles qui vont au fond des choses et fournissent les nécessaires explications, sans concession à la ligne officielle.
OCLC: 1521215335
Keywords: =CL

Courants colonialistes et anticolonialistes dans la pensée républicaine française au tournant du 20e siècle - Aubry, Maximilien (Université de Montréal, 2023)
At the turn of the 19th century, after the fall of the Second Empire, France underwent a period of institutional uncertainty. By trying to consildate the new regime, the founders of the Third Republic engaged the country in a period of colonial expansion. The main promoters of the colonial policy, of which Jules Ferry and Léon Gambetta, try to justify it by integrating universalists republicans principles into the colonial discourse. This method of political persuasion will brought to light its share of contradictions. Historiography on the subject tend to consider that there was a consensus among contemporaries. However, several political actors of the Third Republic will oppose colonial expansion, giving rise to an anti-colonialist current, also inspired by republican thought. The purpose of this dissertation is to examine how two different ideological currents, seemingly contradictory, can define their discourse on the basis of the same philosophical roots. Republican ideology is based upon the principles of the Déclaration des droits de l’homme of 1794, which put forward the concepts of equality and liberty. While these principles were upheld in the colonialist discourse, their application in the colonies was constantly put off. In order not to betray their republican heritage, Third Republic thinkers distorted it, through the concepts of « hiérarchie raciale » and « mission civilisatrice ». Colonialist and anti-colonialist speeches will be analyzed in periodicals and contemporary publications, in addition to numerous speeches from the Chambre des députés (Chamber of Deputies). This dissertation examines studies how republican thought supports both colonialist and anti-colonialist discourse. In that perspective, the analysis of the arguments opposing colonization demonstrates that a stable and lasting anti-colonialist current was clearly present under the Third Republic.
Accepted: 2023-08-02T19:57:10Z
Keywords: =CL; European history / Histoire de l’Europe (UMI : 0335); France; Third Republic; Troisième République; anti-colonialism; anticolonialisme; colonialism; colonialisme; republicanism; républicanisme; universalism; universalisme

La politique des nationalités : vecteur d’expansion internationale du Second Empire français (1859-1868) - Abud, Francis (Université de Montréal, 2012)
The Second French Empire was a period of great change on the international scene in Europe and America. Using the diverse national crises that were shaking the European and American balance of power, Napoleon III intended to use these crises in order to favour French influence in regions where her interests were starting to become vital for worldwide supremacy. Put forward as a means of power, the policy of nationalities is an abstract political idea that creates a political discourse which favors imperial projects around the world. The objective of the policy of nationalities aims at the installation of monarchies allied to France which can be installed in various ways, through war, territorial exchanges or by a new method, popular referenda. However, all of these regimes were installed in the name of nationality. Yet what is innovative in the policy of nationalities, is the systematic recourse to the will of the people as a means to legitimize France’s territorial expansion. This manifested itself in a controlled election or by an assembly of well chosen notables. There was always a need to appear lawful in the eyes of the foreign populations. Using primary sources and a variety of historical studies, this research’s aim is to analyze the methods used by Napoleon III to promote France’s policy of nationalities. We will study the dynamic of this policy and the way the national argument was used during political crises in Italy, Germany, Mexico and the ottoman province of Syria.
Keywords: History - European / Histoire - Européenne (UMI : 0335); Napoleon III; Napoléon III; Second Empire français; Second French Empire; international relations (1851-1870); policy of nationalities; politique des nationalités; relations internationales (1851-1870)

Elf ERAP en Irak, de 1968 à 1977 - Bakka, Karima (Université de Montréal, 2010)
Ever since its creation in 1966, ERAP aimed to increase oil from the “franc” zone by diversifying its supply sources. Such an aim became all the more crucial as its acquisitions in the Sahara seemed threatened by tense relations between the French group and Algerian authorities. Still, to secure a share of the world market at that time seemed to a difficult if not an impossible task, the biggest oil-producing spaces having already been occupied by the big corporations called Majors. However, the French state company managed to settle in several oil-producing countries, including Iraq in 1968, until then viewed as a private hunting ground for the Compagnie française des pétroles (CFP). Also, following its failure in Algeria, the Iraq experiment prompted Elf ERAP to set its sights on oil-rich subsaharian African countries and the North Sea. On February 3rd 1968, Elf ERAP signed an agreement with the state oil company INOC to take charge of exploration and exploitation of a part of the territory that was confiscated by the Iraqi government from the powerful Iraq Petroleum Company (IPC). In return for this financial and technical input/support, Elf ERAP would be rewarded with steady supply of Iraqi oil. It was a new kind of partnership termed « service contract ». The latter replaced the old system of concessions and helped the state company succeed in its attempt to penetrate the Middle East. Exploration quickly led to the discovery of oil fields. Production started in 1976 and reached 5 million tons in 1977.This allowed the Elf ERAP, renamed the SNEA, to look with optimism at its energy supply future, the latter being provided in considerable part by the Iraqi market. Surprisingly, however, the French state company backed away from the deal in May 1977, and was replaced by the INOC which took over the project two years before the date planned by the initial contract of 1968. This research project seeks to clarify the operator role played by ERAP in Iraq between 1968 and 1977. To explain the premature departure of Elf Iraq, one needs to determine both the endogenous and exogenous factors that might have motivated such a move. In other words, did the state company suffer the repercussions of its own energy choices, or was the Iraqi oil policy responsible for such an outcome? To what extent was the withdrawal attributable to the international oil situation? With the help of Elf and TOTAL archives, we have come to the conclusion that the compression of the oil market uniting distributors and producers greatly affected the profitability of intermediary contracts « service contracts».
Keywords: Histoire pétrolière; History - European / Histoire - Européenne (UMI : 0335); Oil history

Aux frontières du mercenariat : éléments de contexte et trajectoires de trois «affreux» français de la sécession katangaise (1960-1963) - Barnay, Martin (Université de Montréal, 2015)
Ce mémoire étudie les origines de l’engagement des combattants de nationalité française en faveur de la sécession du Katanga (1960-63), au moment de l’indépendance du Congo belge. Recrutés pour s’opposer à l’Armée nationale congolaise et aux Casques bleus de l’ONU qui cherchent à faire réintégrer la province par la force, ces hommes aguerris par quinze années de guerre contre-insurrectionnelle vont s’avérer être les éléments clefs du dispositif militaire katangais. Centrée sur les « conditions objectives » de l’action plutôt que sur ses « fondements psychologiques », notre étude vise à mettre en lumière les « forces profondes » au gré desquelles l’intervention des « affreux » a pris forme. Elle s’intéresse en particulier à la trajectoire de trois figures remarquables du point de vue de l'historiographie de l'engagement armé international : Roger Trinquier, Roger Faulques et Bob Denard. Inspirée de la sociologie du champ intellectuel et militant dont elle contribue à montrer la pertinence pour l’étude du fait militaire transnational, notre recherche soutient que le sens de l'engagement ne peut être saisi qu'en replaçant la trajectoire de ces hommes au sein des différents niveaux de contexte dans lesquels elle s’est réalisée. Notre mémoire montre que le recours aux « affreux » coïncide avec le recul des vieilles puissances coloniales sur la scène internationale et avec l'affirmation des nouveaux acteurs que sont les États-Unis, l'URSS et l'ONU. L'engagement de ces hommes, dépourvus de statut officiel, apparaît pour la France comme un moyen détourné de maintenir en Afrique des intérêts et une influence contraire à la dynamique des indépendances.
Keywords: Africa; Afrique; Decolonization; Diplomatic History; Décolonisation; France; Histoire diplomatique; History - General / Histoire générale (UMI : 0578); Mercenaires; Mercenarism

Le Canada et la politique étrangère de la France, 1945-1962 : stratégies d'une puissance moyenne - Beauregard, Daniel (Université de Montréal, 2012)
This study questions Canadian international influence during the "Golden Age" by providing a case study of Canada's foreign policy in its relations with France. Multilateral institutions were the cornerstone of Canadian foreign policy; they were providing the politico-economic counterweights allowing Canadians to distance themselves from the United States. These institutions were often perceived as a constraint by the French, who consequently tried to weaken or reform them. Meanwhile, they were trying to preserve their colonial empire and were demanding unanimous occidental support. France became the most disturbing of Canada's allies, almost systematically attacking its foreign policy project, which consisted in trying to balance a firm commitment to NATO and an overtly anti-imperialist policy designed to seduce non aligned countries of the Commonwealth. This dissertation studies the strategies of a "middle power" trying to defuse the crisis between its allies and to reconcile the contradictory dimensions of its own external policy.
Keywords: Atlanticism; Atlantisme; Canada; Commonwealth; Decolonization; Décolonisation; France; History - Canadian / Histoire - Canadienne (UMI : 0334); Middle power; Multilateralism; Multilatéralisme; NATO; OECE; OEEC; ONU; OTAN; Puissance moyenne; UN

La politique européenne du président de Gaulle dans la première moitié de sa présidence : perception de trois journaux français 1958-1964 - Bianki, Patrick (Université de Montréal, 2006)
Keywords: Charles de Gaulle; Communauté économique européenne (CEE); France; Journaux

Le regard de l'allié britannique sur la France et son armée durant la guerre de Crimée - Bérubé, Simon (Université de Montréal, 2012)
In the Crimean war, Great-Britain made an alliance with the Second French Empire, the traditional enemy, still considered as a threat; this cooperation, forced by circumstances, forms the basis of this research. Thousands of soldiers and civilians from both countries worked together for two years. The British personal letters reveal a fraternization between both cultures that is more important than the one mentioned in the historiography. According to Gordon Allport’s theories on the diminution of prejudices, all the necessary conditions for reconciliation could be found in Crimea. The steps leading to the fraternization, defined by Allport, are also perceptible in the personal letters. This reconciliation had under-estimated consequences: British soldiers and civilians started comparing themselves with the French and their pride gave place to an important self-criticism. This led to scandals in the army and the newspapers from the very beginning of the war, long before the scandals of the winter 1854-1855.
Keywords: Army; Armée; Cooperation; Coopération; Correspondance; Correspondence; Enemies; Ennemis; Francophile; Francophilie; Francophobia; Francophobie; Grande-Bretagne; Great-Britain; History - European / Histoire - Européenne (UMI : 0335); Prejudice; Préjugés; Reconciliation; Réconciliation; Second Empire; Second French Empire

L'économie et l'État-nation : les gaullistes post-de Gaulle et l'intégration européenne (1976-1988) - Blanc, Valérie (Université de Montréal, 2007)
Keywords: Crise économique; Gaullisme; Gaulliste; Intégration européenne; Rassemblement pour la République (RPR); Relations internationales; Économie Ve République

Le nationalisme arabe, vu par L'Humanité et Le Populaire (1945-1962) - Boisjoli, Andréanne (Université de Montréal, 2003)
Keywords: Communisme; Décolonisation; France; Socialisme; États arabes

Le Commissariat général à l'information comme agent de renforcement du moral français - Boivin, Sébastien (Université de Montréal, 2007)
Keywords: Commissariat général à l'information; Deuxième guerre mondiale; Défaite française; France; Moral; Opinion publique; Presse; Propagande

Analyse du regard de trois quotidiens français sur l'Algérie postcoloniale : 1962-1971 - Chabalier, Jaurès (Université de Montréal, 2012)
The collapse of the French colonial empire begins in the 1950s. After losing its colonies in Morocco and Indochina, France was faced with the secession of its most important colony, Algeria. The French had difficulty accepting the separation as it not only represented the fall of the colonial empire, but the destruction of cherished dreams. More than fearing losing their status as a colonial power, the French fear they will also lose their world great power status and their vision of being a country with a mission civilisatrice. To understand the evolution in the perception the French had of Algeria after the Algerian decolonization through various schools of thought, this thesis looks at editorials published in three French newspapers (Le Figaro, L’Humanité and Le Monde) between 1962 and 1971, which covered events taking place in Algeria. More specifically, this thesis examines OAS terrorist action in the period between the Évian Accords and the Algerian referendum, the conflict within the National Liberation Front (FLN) to decide who would be in power, the conflict with the Socialist Forces Front (SFF), the war with Morocco, the Boumedienne coup d’état and the nationalization of Algerian oil.
Keywords: Algeria; Algérie; Ben Bella; Boumedienne; Colonisation; Colonization; Decolonization; Décolonisation; FLN; France; French journals; History - European / Histoire - Européenne (UMI : 0335); Journaux français; Le Figaro; Le Monde; L’Humanité; OAS

Étude comparative des campagnes napoléoniennes d'Iéna et Waterloo - Chalvardjian, Eugène (Université de Montréal, 2006)
Keywords: Angleterre; France; Iéna; Prusse; Stratégies et tactiques militaires; Waterloo

La guerre d'Algérie vue par le New York Times et le Times (1954-1962) - Bussière, Réjean (Université de Montréal, 2002)
Keywords: Histoire

Impact de l'art de la guerre napoléonien dans la seconde moitié du XIXe siècle - Chalvardjian, Eugène (Université de Montréal, 2013)
Le 18 juin 1815, Napoléon fut renversé à Waterloo, mais son art de la guerre survécut. Il s'agit de cet art militaire qu'il avait révolutionné et dont d'autres firent de nombreuses applications longtemps après sa disparition. S'inspirant des méthodes des théoriciens du XVIIIe siècle, il avait privilégié la stratégie d'anéantissement dans la conduite d'opérations militaires et se classait ainsi dans la catégorie des stratèges recherchant avant tout la bataille décisive en vue de détruire les forces ennemies. À la lumière des tactiques et stratégies que Bonaparte utilisa dans ses plus célèbres campagnes, cette thèse tentera de dégager les méthodes napoléoniennes qui furent le plus souvent utilisées au cours de la seconde moitié du XIXe siècle. Les conflits étudiés durant cette période seront la guerre de Crimée (1853-1856), la campagne d'Italie (1859), la guerre de Sécession américaine (1861-1865), la guerre austro-prussienne (1866) et la guerre franco-prussienne (1870-1871). Cette recherche tiendra compte non seulement de l'influence des progrès de l'armement et des moyens de transport et de communication sur l'art de la guerre en général, mais aussi du contexte économique, financier, politique et militaire des États bélligérants de cette époque. Parmi les nombreux exégètes de Bonaparte du XIXe siècle, deux théoriciens militaires en particulier, Clausewitz et Jomini, se distinguèrent dans l'interprétation savante de la guerre napoléonienne. Tout en analysant l'impact des méthodes de l'Empereur dans les guerres selectionnées, nous allons déterminer dans quelle mesure la vision jominienne des campagnes de Bonaparte divergeait de celle de Clausewitz en ce qui concerne les conflits traités. Nous aborderons ensuite l'influence napoléonienne sur l'administration, l'organisation et les marches des armées impliquées dans les guerres en question et nous porterons une attention particulière à l'impact du système militaire de Bonaparte sur certains aspects du déroulement même des combats. Nous terminerons cette étude par un bref aperçu sur les enseignements que les militaires au XIXe siècle purent dégager des campagnes napoléoniennes pour la conduite des guerres de l'avenir.
Keywords: Angleterre; Annihilation strategy; Austria; Autriche; England; France; History - Military / Histoire - Militaire (UMI : 0722); IItaly; Italie; Napoleon I; Napoléon 1er; Offensive tactics; Prusse; Prussia; Russia; Russie; Stratégie d'anéantissement; Tactiques offensives; United-States; États-Unis

L'historiographie française du Second Empire français : de la légende noire à la restauration - Corriveau, David (Université de Montréal, 2017)
La perception du Second Empire français a longtemps été sujette à controverse dans l’historiographie française. Alors que le régime a été synonyme de honte nationale pendant plusieurs décennies, l’historiographie en a tracé un portrait peu flatteur qui a tardé à évoluer. Cette interprétation négative dure jusqu’aux années 1930-1940, à partir desquelles les historiens remettent en question les idées reçues sur le régime et le perçoivent positivement. En effectuant une critique externe et interne d’ouvrages publiés par des auteurs français sur le Second Empire depuis 1870, le présent mémoire vise à identifier les facteurs qui expliquent la lente transformation de la perception du régime et de l’Empereur. La critique externe démontre que les auteurs, le contexte historique et la discipline historique ont joué un rôle dans cette perception. L’analyse interne de la politique socio-économique, intérieure et extérieure du régime, ainsi que de la personnalité de l’Empereur, démontre que d’autres facteurs, comme l’utilisation de sources et la façon d’aborder le sujet, ont eu un impact sur l’évaluation de Napoléon III et du Second Empire.
Keywords: Historians; Historiens; Historiographie; Historiography; History - European / Histoire - Européenne (UMI : 0335); Louis-Napoleon Bonaparte; Louis-Napoléon Bonaparte; Légende noire; Napoleon III; Napoléon III; Second Empire français; Second French Empire

Les relations monétaires franco-allemandes et l’UEM (1969-1992) : des ambitions aux réalités - Coën, Alain (Université de Montréal, 2021)
In 1969, in a well-established European Economic Community (EEC) under the neo-Gaullist presidency of Georges Pompidou, Germany stood as a model for France, looking for an effective industrial policy and a recovery of its rank on the international scene. Since the mid 1960s the international monetary system had been weakened by the growing US debt. France wanted to be the leader of the economic and monetary union (EMU). This political decision was a means to improve its economy confronted with the instability of the international monetary system. As pointed out by Jacques Rueff, « L’Europe se fera par la monnaie ou ne se fera pas. » During this period, from the relaunch of the EMU (December 1969) to the Maastricht Treaty (February 1992), French economic action was based on a strong political will defined to reinforce the relationships with the Federal German Republic, and then the reunified Germany. The Franco-German monetary relationships aimed to promote a strong and independent Europe and to restore an exchange rate stability. The “golden standard” stability myth was viewed and understood differently in France and Germany. If recent historical studies have been partially devoted to the consequences of European monetary policies (essentially in France) on economic and monetary integration in the EEC, they focused on the 1974-1981 or 1981-1986 periods. The creation of the EMU was a dynamic process running from December 1969 to February 1992. Franco-German monetary relationships included two levels of decision-making. First, on the political level, there was the presidency, the chancellery, the European Commission and the ministers. Second, its counterpart, economic power. The latter requires analysis of the role played by central banks in the definition and application of monetary policies. This dichotomy illustrates the progressive transition between the political level and the economic level during the 1980s. The decline of politics and the primacy of economics were analyzed differently in France and Germany. Political and economic objectives and expectations were contrasted and divergent. This study demonstrates that the EMU dynamic was an economic process where politics gave way to economics. Monetary relations were asymmetric. The real interlocutor of French political authorities was German economic power, represented by the Bundesbank. The Franco-German tandem was a political myth broken by world economy liberalization. For Germany, the EMU was a device to define a European Germany in a federal Europe. In France, it represented an illusory means to restore French primacy for conservative and liberal governments and a way of compensating a failing ideology for socialist governments. The EMU provided monetary stability, but the dream of a powerful and independent Europe vanished with the Maastricht treaty. Even as it rejected the idea of European political union defended by the German diplomacy, France paradoxically laid the foundations of a German Europe.
Keywords: European monetary system (EMS); European monetary union (EMU); French monetary policy; German monetary policy; History - European / Histoire - Européenne (UMI : 0335); Maastricht treaty; Système monétaire européen (SME); Traité de Maastricht; Union européenne; Union économique et monétaire (UEM); politique monétaire allemande; politique monétaire française

La décolonisation au Mali et au Sénégal, 1958-1962 : essai d'explication d'une évolution politique contrastée - Dagenais, Dominic (Université de Montréal, 2006)
Keywords: Décolonisation; Indépendance; Mali; Néocolonialisme; Socialisme; Soudan; Sénégal; Unité africaine

Waterloo : la bataille de tous les enjeux - Cyr, Pascal (Université de Montréal, 2008)
Keywords: 1815; 1er Empire; Armée française; Campagne de Belgique; First Empire; France; French Army; French Revolution; Hundred Days; Napoleon; Napoléon; Révolution Française; Waterloo; Wellington

La guerre américaine au Vietnam dans l'historiographie française des années 1960-1970 et 1990-2000 - Desjardins, Léa (Université de Montréal, 2016)
Le mémoire historiographique qui suit a comme sujet principal l’étude de l’évolution des perceptions françaises sur l’implication américaine au Vietnam. Nous nous sommes basés sur l’historiographie de deux périodes distinctes, soit celles des années 1960-1970 et 1990-2000. L’objectif était de voir s’il y a eu une transformation du regard que portent les auteurs sur l’implication américaine et, si oui, quelles en sont les causes. Le travail est construit de façon thématique et se divise en trois chapitres. Le premier aborde le choix et l’ampleur des armes utilisées, le second se penche sur la notion du communisme et de la démocratie, et le dernier traite de la conception de l’impérialisme et du colonialisme. Pour tous les thèmes examinés, nous résumons la perception qui ressort de chacun des auteurs afin de comparer les tendances idéologiques propres aux deux périodes étudiées. Nous conclurons qu’il s’est effectivement produit une importante transformation des perceptions. Cette transformation se traduit par une approche de moins en moins critique envers l’implication américaine au Vietnam. Dans chaque chapitre, nous avons pu soulever des causes de changement propres au sujet abordé. Toutefois, une tendance générale et sous-jacente se dégage et s’avère des plus révélatrices, soit le glissement en France des valeurs politiques et morales de la gauche vers la droite, doublé d’un rapprochement idéologique avec les États-Unis.
Keywords: Engineering - Agricultural / Ingénierie - Agricole (UMI : 0539); France; Guerre du Vietnam; Historiographie; Historiography; Perception; USA; Vietnam War; États-Unis

Les relations franco-japonaises de 1859 à 1895 - Forest, Patrick (Université de Montréal, 2015)
L’histoire des relations franco-japonaises est source de bien des surprises pour les historiens, ces deux pays n’ayant, à première vue, que peu de raisons de se rapprocher. La France du Second Empire est l’une des premières puissances à se rendre au Japon et elle démontre rapidement un vif intérêt pour le développement du Japon. Dès la signature des premiers traités en 1859, la présence française se développe pour atteindre son sommet quelques années plus tard. Malgré les changements de régime au Japon et en France, cette présence restera forte jusqu’au début des années 1880, avant de décliner. Qu’est-ce qui explique cet intérêt? Et, surtout, qu’est-ce qui explique le désintérêt de la France après les années 1880? Il n’y a que quelques auteurs qui ont tenté d’y trouver des réponses, et celles-ci sont, à notre point de vue, peu concluantes: soit la France agit pour faire grandir son prestige, soit elle agit en fonction de ses représentants. Nous tenterons dans le présent travail de cerner et, si possible, de trouver en utilisant une variété de sources françaises une autre cause plus convaincante comme explication de la position française au Japon. Serait-ce le commerce qui a motivé la France au Japon, notamment à cause de la crise du ver à soie? Serait-ce la religion, avec toute la question des persécutions des chrétiens? Ou encore, est-ce une raison plus globale liée à la colonisation de l’Indochine? Afin d’y répondre, nous avons étudié avec minutie les archives du gouvernement français ainsi que les données économiques de l’époque, afin de cerner l’importance qu’ont eue certaines raisons, telles la crise de la soie, les persécutions religieuses et la présence française en Indochine, dans les décisions du gouvernement français.
Keywords: Christianity; France; History - Modern / Histoire - Moderne (UMI : 0582); Japan; Japon; christianisme; commerce; silk; soie; trade

Les militaires français et la Communauté européenne de défense, 1950-1954 - Gagné, Nicolas (Université de Montréal, 2019)
This thesis studies the European Defence Community (EDC), a plan for a European supranational army proposed by French politicians in October 1950 and rejected by the French National Assembly in August 1954. It is more precisely concerned with the position of the French army, a group directly concerned by the project. The subject has been relatively neglected by historians. The army was being asked to pursue two contradictory tasks: fight alongside its allies the threat the Soviet Union was supposed to represent without sacrificing its independence. This thesis will focus, among other things, on the arguments presented for and against the EDC, the differences of opinion within the army, the factors that might account for these differences, the relative importance of the supporters and detractors of the project, and the variables taken into consideration by the members of the army on both sides (the communist threat, national power, colonial power, supranationalism, independence, etc.) It is based on the archives of the Service historique de la Défense (SHD), located in Vincennes, near Paris. This thesis shows that, although a majority clearly opposed the EDC, there was also a significant pro-EDC current, whose importance has often been underestimated by historians, and that both sides primarily used political arguments.
Keywords: CED; EDC; France; French Union; History - European / Histoire - Européenne (UMI : 0335); Union française; anticommunism; anticommunisme; army; armée; indépendance nationale; national independence; supranationality; supranationalité

La présentation de la commémoration du 11 novembre dans la presse au Canada et en France : une étude comparative (1919-1999) - Gagnon, Christian (Université de Montréal, 2001)
Keywords: Histoire

La loi mémorielle de 2005 et la réaction des historiens. Perspective sur la pédagogie de la mémoire dans les cours d'histoire - Héroux, Pascal (Université de Montréal, 2014)
La loi mémorielle du 23 février 2005 a créé une grande controverse en France. Les historiens furent le fer de lance de cette opposition, tant cette loi heurtait les fondements même de leur profession. En effet, la loi de 2005 préconisait l’obligation pour ceux-ci d’enseigner le rôle positif de la colonisation française, ce qui contrevient à la liberté de pensée indispensable à la fonction de l’historien. Le présent mémoire analyse la réaction des historiens afin de cerner leurs positions et leur compréhension de la crise. Il porte un nouveau regard sur la crise mémorielle de 2005 et évalue les écrits et actions des historiens. Il s’avère que la crise fut plus complexe que l’interprétation que lui ont donnée les historiens. À cet égard, l’étude souligne l’importance de l’espace public dans la relation entre les communautés mémorielles et les historiens. A ce titre, l’école symbolise ce lieu de rencontre entre histoire et mémoire. Le mémoire examine aussi l’enseignement de l’histoire dans un milieu scolaire affecté par les tensions mémorielles. En réponse à ces débordements de mémoire, l’historien a un devoir de rigueur intellectuelle autant à l’école que dans l’espace public en général.
Keywords: Colonisation; Colonization; Enseignement; France; History - European / Histoire - Européenne (UMI : 0335); Law; Loi; Memory; Mémoire; Teaching

Les historiens français et britanniques devant la responsabilité de l’échec des négociations tripartites de 1939 : étude historiographique de 1961 à 2011 - Hince, Alexandre (Université de Montréal, 2016)
En 1939, la France et la Grande-Bretagne réalisent que, pour arrêter les agressions d’Hitler en Europe, il va leur falloir constituer un front commun. Cette recherche d’alliés les mène à courtiser l’Union soviétique. Malgré plus de quatre mois de négociations anglo-franco-soviétiques, aucune entente n’intervient entre les parties. Cet échec est d’autant plus douloureux que le 23 août un pacte de non-agression est signé entre Berlin et Moscou et, qu’une semaine plus tard, l’Allemagne envahit la Pologne. La Seconde Guerre mondiale est commencée. Depuis les années 1990, plusieurs historiens ont affirmé que l’historiographie occidentale concernant l’échec des négociations tripartites de 1939 a été influencée par la propagande de la Guerre froide et qu’elle avait propagé l’idée que les Soviétiques n’avaient jamais eu l’intention de s’allier avec l’Entente. Toutefois, après l’analyse des études publiées entre 1961 et 2011 par les historiens français et britanniques, ce mémoire démontre que, depuis 1961, en Grande-Bretagne et en France, l’interprétation du rôle de l’Union soviétique dans cet échec est beaucoup plus libre d’aprioris idéologiques qu’on pourrait le croire. La publication de l’ouvrage d’A.J.P. Taylor, The Origins of the Second World War, et la controverse qu’il va causer ont radicalement modifié la nature du débat et permis l’ascendant de thèses en tous points semblables à celles qui ont cours en Occident depuis le démantèlement de l’Union soviétique. Celles-ci soutiennent que les dirigeants soviétiques ont priorisé une alliance avec l’Entente au moins jusqu’à la fin du mois de juillet et que ce sont les politiques étrangères de la France et, plus particulièrement, de la Grande-Bretagne, qui ont causé l’échec des négociations tripartites de 1939.
Keywords: 1939; France; Grande-Bretagne; Great Britain; History - European / Histoire - Européenne (UMI : 0335); URSS; USSR; cause/origine de la Seconde Guerre mondiale; historiographie; historiography; international relations; origin of the Second World War; relations internationales

La politique française envers les États pontificaux sous la Monarchie de Juillet et la Seconde République (1830-1851) - Jolicoeur, Nicolas (Université de Montréal, 2006)
Keywords: Monarchie de juillet; Pouvoir temporel (1849); Question romaine; Seconde république; États pontificaux

L'attitude de la presse française face à l'indépendance belge de 1830 - Jolicoeur, Nicolas (Université de Montréal, 2000)
Keywords: Histoire

Par rapport au monde : la dimension internationale comme point de ralliement entre la Résistance intérieure et le général de Gaulle (1940-1944) - Houle, Vincent (Université de Montréal, 2017)
Suite à la sévère et foudroyante défaite aux mains de l’Allemagne pendant la Seconde Guerre mondiale, des mouvements de résistance, refusant l’armistice, se sont organisés en France pour s’opposer à l’occupation nazie puis au régime de Vichy. Exilé à Londres, Charles de Gaulle réussit, entre 1940 et 1944, à s’imposer comme le chef de ces organisations résistantes. Le présent mémoire propose d’analyser le processus de ralliement au gaullisme à travers de nouveaux questionnements, en explorant le rapport que la Résistance intérieure française entretient avec le monde ainsi que la manière dont les facteurs internationaux influencent l’adhésion des résistants français au général de Gaulle. Notre étude, basée sur l’analyse du contenu de la propagande clandestine et de la France libre, expose l’importance qu’elles accordent aux sujets internationaux et à leur association favorable au général de Gaulle. Elle révèle en outre la présence de liens étroits entre le rapport de la Résistance intérieure au monde et ce qu’incarne pour elle le général de Gaulle. Notre analyse montre ainsi l’influence significative des facteurs internationaux dans le processus de ralliement de la base résistante au gaullisme. Apportant nuances et précisions à la conception politique traditionnelle des liens entre la Résistance intérieure et le général de Gaulle, notre mémoire permet une compréhension plus complète du phénomène résistant en France.
Keywords: France; French Resistance; General de Gaulle; Général de Gaulle; History - European / Histoire - Européenne (UMI : 0335); International; Résistance française; Second World War; Seconde Guerre mondiale

La stratégie pétrolière de la France en Algérie, 1962-1971 - Kabbanji, Jad (Université de Montréal, 2017)
After an eight-year war, Algeria gained full independence. Saharan oil, a major reason for the extension of the war, became the property of the new independent republic. On the other hand, French petroleum companies, which had a quasi-monopoly over the oil industry, kept their former privileges. Nevertheless, the Evian Accords of March 1962, which guaranteed these privileges, were challenged by the new Algerian authorities meeting in Tripoli, Libya, a few months later. This was in line with the will of the Algerian governing party to nationalize the gas and oil industry. Finally the adoption of the socialist path by the new leadership, in addition to the departure of the majority of the European population, compromised the French strategy to keep control of Saharan supplies, the more so that they were payable in French francs. This thesis asks the following question: what strategies did France adopt to safeguard its interests in anticipation of the nationalization of the oil industry it considered inevitable? A chronological approach makes it possible to show the evolution of Franco-Algerian relation in the field of oil between 1962 and 1971. Sources are mainly the archives of the French petroleum company TOTAL and the French Foreign Affairs ministry. For the Algerian side, it makes uses of the personal archives of the Algerian minister of industry and energy at the time, Abdesselam Belaïd. The dissertation demonstrates that, starting from the beginning of 1960’s, the main goal of France was to diversify its sources of supply and to diminish its dependency towards Algerian oil. Saharan resources were part of the strategy. In addition, this research shows that, starting in the middle of the 1960’s, French petroleum companies diminished their level of engagement in Algeria to the minimum. Finally, the thesis highlights the limits of the French strategy of diversification of its oil supply.
Keywords: Algéria; Algérie; Diversification; France; History - European / Histoire - Européenne (UMI : 0335); Nationalisation; Nationalization; Petroleum; Pétrole

Les négociations entre l'Iraq Petroleum Company et le Liban et la Syrie durant les années 1950 - Kabbanji, Jad (Université de Montréal, 2008)
Keywords: Arab nationalism; Charge; Cléoducs; Economy; Imperialism; Impérialisme; Iraq; Lebanon; Liban; Nationalisme arabe; Negotiation; Négociation; Oil; Petroleum Company; Pipeline; Pétrole; Redevance; Syria; Syrie; Économie

L’influence du système scolaire français sur le système scolaire iranien de l’inauguration de l’école Dar ol-Fonoun jusqu’à la fin de l’époque des Qâdjârs (1851-1925) - Koochakzadeh, Leila (Université de Montréal, 2017)
La présente thèse de recherche concerne l’évolution du système éducatif iranien à l’époque des Qâdjârs, et étudie notamment le rôle qu’y ont eu la France et les acteurs français. Il s’agit de mettre en, exergue l’influence du système éducatif français sur celui de l’Iran, sans pour autant être une comparaison de ces deux systèmes. Ce travail est une recherche historique, qui prend pour but d’étudier le processus de formation d’une structure scolaire moderne en Iran de 1851 à 1925. En prenant contact avec l’Occident, l’Iran du début du XIXème siècle cherche à combler son retard par rapport aux pays européens industrialisés, en leur empruntant savoirs, technologies et méthodes. La mise en place d’un système éducatif radicalement différent de la structure préexistante des écoles coraniques, dites maktab, participe de ce mouvement et est vue par les élites progressistes comme une condition sine qua non à la modernisation du pays. Le modèle éducatif français leur apparait comme étant le meilleur à suivre, et avec lui se diffusent dans le pays la langue et la culture française. Dans cette thèse de doctorat, nous entendons d’abord analyser l’arrière-plan sociopolitique à la mise en place d’un nouveau système scolaire, via la fondation d’écoles modernes, en Iran. Nous tâchons ensuite d’étudier les modalités de mise en œuvre de ce système par les acteurs aussi bien étatiques que privés, tant français qu’iraniens.
Keywords: Ecole; Education; France; History - Middle Eastern / Histoire - Moyen-orientale (UMI : 0333); Iran; Modernity; Modernité; School

La France et la Méditerrannée : objectifs politiques et stratégiques, 1930-1940 - Laberge, Martin (Université de Montréal, 2006)
Keywords: Allemagne; Armée; Balkans; Deuxième Guerre mondiale; Entre-deux-guerres; Grande-Bretagne; Italie; Marine; Relations internationales; Turquie

La perception du boulangisme par la presse britannique - Lagrange, Catherine (Université de Montréal, 2017)
Au cours de la deuxième moitié des années 1880, la vie politique française est marquée par l’émergence du boulangisme. Ce mouvement contestataire éphémère, qui se forme autour du général Boulanger, rassemble aussi bien des membres de la gauche que de la droite grâce à un programme qui se résume principalement au slogan «Dissolution, constituante, révision». En s’opposant au régime parlementaire des républicains modérés, le boulangisme menace la Troisième République et suscite également des craintes à l’échelle européenne, alors qu’on appréhende qu’une victoire du «général Revanche» n’entraîne, volontairement ou non, une nouvelle guerre européenne. Ce mémoire vise à approfondir les connaissances sur la perception du boulangisme hors France en analysant le contenu de quatre journaux britanniques (le Birmingham Daily Post, le Manchester Guardian, le Scotsman et le Times) qui ont été choisis afin d’assurer une représentation géographique et politique. Les deux premiers chapitres abordent la perception de l’impact du boulangisme sur la scène européenne et sur la scène politique française, alors que le dernier chapitre s’attarde à l’image que se fait la presse britannique du général Boulanger comme individu. Ce qui se dégage de cette analyse est une perception principalement négative du boulangisme.
Keywords: Boulangism; Boulangisme; France; General Georges Ernest Jean-Marie Boulanger; Grande-Bretagne; Great Britain; Général Georges Ernest Jean-Marie Boulanger; History - European / Histoire - Européenne (UMI : 0335); Perception; Press; Presse

Les relations franco-polonaises 1944-1947 : rapports bilatéraux à l'ère de la naissance des blocs - Michalec, Tomasz (Université de Montréal, 2002)
Keywords: Europe; France; Guerre froide; Nationalisation; Négociations socio-économiques; Pacte d'amitié franco-polonais; Pologne; Quai d'Orsay; Relation bilatérale; Seconde guerre mondiale; URSS

Considérations économiques et décolonisation en Afrique subsaharienne, 1956-1960 : la perception des dirigeants français - Mireault, Ghislain (Université de Montréal, 2005)
Keywords: Afrique; Décolonisation; France; Économie

La montée du fascisme en Italie, perçue par les journaux français - Pelletier, François (Université de Montréal, 2014)
L’apparition et la montée du fascisme en Italie sont des faits marquants du XXe siècle et plus précisément de l’entre-deux-guerres. Ce nouveau phénomène social a rapidement attiré l’attention de la communauté internationale. Il vient frapper les mentalités européennes dans le contexte de sociétés déjà polarisées par divers courants idéologiques. La Première Guerre mondiale a fait place à de fondamentales divergences d’opinions sur ce que devait être le futur, autant social qu’économique, des sociétés industrielles. S’étant imposé en Italie, le fascisme représente un de ses mouvements. Ce travail s’intéresse à la manière dont la société française a perçu la montée du fascisme italien. Pour ce faire, il retrace l’approche de plusieurs journaux français de 1919 à 1926 à l’égard de l’expérience italienne. L’analyse des grands journaux Le Temps, L'Humanité, Le Figaro et L'Action française permet un survol de l’opinion politique en France. La problématique avancée dans ce travail nous aide à en apprendre plus, non seulement sur l’apparition d’un phénomène majeur du siècle précédent, mais aussi, plus précisément, sur le regard porté sur lui par les grands courants politiques français. On a pu déceler plusieurs thèmes de prédilection abordés par la presse française. Premièrement, celle-ci a tenté de définir le fascisme, son origine et sa composition ainsi que le phénomène de la violence qui touchait la péninsule. Puis, le fascisme ayant accédé au pouvoir, elle a réfléchi sur le coup de force et ses répercussions. Finalement, elle a analysé la politique intérieure et extérieure du nouveau régime. Il en ressort une perspective unique grâce à l'analyse de quatre organes majeurs qui représentent et façonnent l'opinion publique en France. Notre analyse montre que le fascisme est un sujet préoccupant pour les contemporains par son caractère nouveau. Tous les journaux ont suivi l'évolution de ce mouvement avec attention. Les réactions en témoignent: ce fut, entre autres, l'exemple frappant d'une répression brutale pour les uns et l'émergence d'une idéologie susceptible de mettre fin à la terreur du bolchevisme pour les autres. Ce fut aussi un terrain d'affrontement idéologique.
Keywords: France; History - European / Histoire - Européenne (UMI : 0335); Italy; Mussolini; fascism; fascisme; italie; journaux; newspapers

Les industriels du coton et le Traité de commerce franco-anglais de 1860 - Petitpas, Philippe (Université de Montréal, 2004)
Keywords: Coton; Industriels; Libre-échange; Protectionnisme

Industries et industriels français du textile face au défi international 1871-1914 - Petitpas, Philippe (Université de Montréal, 2012)
Fortement liées à l’international, les industries françaises du textile ont connu une évolution erratique entre 1871 et 1914. L’adoption de tarifs hautement protectionnistes en 1892 favorise les industriels du coton au détriment de ceux travaillant la laine et la soie. Ces derniers exportent leurs marchandises luxueuses sur des marchés ouverts à la concurrence. Ils profitent peu des marchés coloniaux, moins intéressés par leurs produits. Des politiques hardies d’importation directe de la matière première permettent, notamment à Roubaix, de pallier à certains désavantages. Si plusieurs industriels incitent le gouvernement à réformer ses services commerciaux à l’étranger et à y adjoindre des spécialistes, ils retiennent peu les recommandations des experts concernant l’adoption des moyens propres à favoriser les exportations. Plusieurs carences du commerce français ont été soulignées précocement mais il a été difficile de rapidement appliquer des solutions. Dans un contexte marqué par une concurrence accrue sur les marchés extérieurs, la France s’en tire mieux qu’on a pu le penser. La flexibilité de l’appareil productif français permet d’obtenir de nombreuses commandes dans les créneaux du luxe et du demi-luxe. Son niveau d’intégration, moins élevé que dans d’autres pays, se révèle ainsi parfois être un avantage. Toutefois, l’industrie textile est handicapée par la grande difficulté des patrons à s’associer de manière stable à l’extérieur du clan familial. L’entente se réalise cependant plus aisément et avantageusement pour ceux qui ont une production spécialisée, rare ou brevetée. Les performances et l’organisation des entreprises textiles françaises à l’étranger montrent que le marché national stimulait peu les producteurs à adopter les meilleures conditions de production possibles. Ces sociétés et celles obtenant des succès à l’exportation sont souvent les plus dynamiques et les plus rentables.
Keywords: Commerce extérieur; Coton; Cotton; Foreign trade; France; Free trade; History - European / Histoire - Européenne (UMI : 0335); IIIe République; Industrie; Industriels; Industry; Laine; Libre-échange; Manufacturers; Silk; Soie; Textile; Third Republic; Wool

Adaptation et immutabilité en droit musulman : illustrées par l'expérience marocaine - Poupart, André (Université de Montréal, 2009)
Keywords: Charia; Civil law; Code du statut personnel (Mudawana); Common law; Coran; Droit; Droit civil; Evolution; Immutability; Immutabilité; Law; Laïcisation; Maroc; Secularization; Shari'a; Évolution

La perception de la puissance de l'Union soviétique par les milieux diplomatiques français et britannique de 1933 à 1939 - Pinet, Raphaël (Université de Montréal, 2006)
Keywords: France; Grande-Bretagne; Puissance; Relations internationales; URSS

Investissements privés et occupation étrangère : les milieux d'affaires français et l'intervention militaire en Russie, 1917-1920 - Poirier, Adrien (Université de Montréal, 2021)
In 1917, the Bolshevik party seized power in Russia, repudiated state debt, nationalized private enterprises and imposed early forms of Soviet management to the economy. France, whose economic ties with Russia had largely grown during the three previous decades, saw her huge investments in the country compromised. The French private sector, by far the most affected of all Allied powers, reacted strongly to this regime change. This memoir focuses on the subsequent actions of the private sector, and seeks to understand how they reacted to the Bolshevik’s coming to power. Did they play a role in the process of decision-making towards military intervention? Did they have any impact on the ground in Russia? How did they react to the ultimate failure of the intervention and the loss of their assets? We demonstrate that the economic factor was central in the adoption of an interventionist policy. We also examine how the French government discreetly tried to support the private sector, but mostly used it to advance its own interests in Russia. Finally, we demonstrate that the failure of the private sector to defend its interests has many common causes with the failure of the military intervention itself.
Keywords: French intervention; Guerre civile russe; History - Russian and Soviet / Histoire de la Russie - histoire soviétique (UMI : 0724); Military occupation; Russian civil war; intervention française; intérêts privés; occupation militaire; private interests

La politique culturelle de la France en Algérie : les objectifs et les limites (1830-1962) - Risler, Camille (Université de Montréal, 2000)
Keywords: Histoire

Les possessions françaises en Inde dès les années 1920 jusqu'à l'indépendance : histoire d'un revirement politique - Stech, Zorian (Université de Montréal, 2011)
Peu de personnes se rappellent de la présence de la France en Inde. Quelques parties de l’Inde sont restées françaises jusqu’en 1954. À cette date, l’Inde française, consistant de quatre petits établissements (Pondichéry, Yanaon, Karikal et Mahé), était en pleine décadence et éclipsée par d’autres colonies françaises, plus grandes, plus lucratives et plus importantes pour la Métropole. L’Indochine et l’Algérie ne sont que deux exemples. Toutefois, les Français n’étaient pas disposés à abandonner leurs possessions en Inde sans résistance. Le présent mémoire cherche à expliquer la valeur des possessions françaises en Inde et les raisons de la fin de la tutelle française. Le titre du mémoire indique qu’un certain changement a eu lieu dans la politique française vis-à-vis de ses possessions en Inde. L’étude commence par un résumé de la situation politique et économique de l’Inde française depuis la fin de la dernière occupation anglaise en 1814 jusqu’à la fin de la Première Guerre mondiale. L’année 1920 est choisie comme point de départ de la période visée par le mémoire. Portant sur les années 1920, le premier chapitre examine l’hégémonie du parti Gaebelé qui a eu toutes les caractéristiques d’une dictature. Indifférentes à la vie politique de l’Inde française, les autorités métropolitaines étaient surtout attirées par le commerce que la colonie offrait dans la production de tissus et l’exportation d’arachides. Après la chute du parti Gaebelé, l’Inde française a été plongée dans une longue période d’agitation, un thème clé du deuxième chapitre sur les années 1930. Inconscientes de la réalité politique, les autorités métropolitaines ont toujours accordé la priorité au commerce. Durant les années 1940, l’Inde française n’a jamais arrêté de se rapprocher de l’Inde britannique. Ce rapprochement a aussi persisté lorsque l’Inde britannique est devenue l’Union indienne en 1947. Soudainement, les Français ont senti le besoin de réaffirmer leur position d’autorité en Inde française. Le commerce est passé au second plan au profit d’une série de réformes politiques. Toutefois, ce brusque changement de politique fut trop tardif. Le quatrième chapitre, centré surtout sur la période de 1950 à 1954 et vu à travers l’exemple d’Édouard Goubert, a souligné la méconnaissance des autorités métropolitaines des réalités qui confrontaient l’Inde française. Lorsque Goubert a cessé de servir comme porte-parole et principal allié du gouvernement français en Inde, les possessions françaises en Inde furent rattachées une par une à l’Union indienne. Rétrospectivement, les faits économiques, vitaux pour le début du mémoire, sont quasiment absents de deux derniers chapitres. Se retrouvant face à la menace de perdre leurs possessions en Inde, les Français ont compris que l’Inde française était précieuse pour des raisons autres que le commerce. Un accent particulier fut mis pour souligner ces avantages culturels et politiques. De petite taille, les possessions françaises étaient importantes pour l’ordre et la stabilité dans les autres colonies de l’Empire. Parallèlement, elles représentaient des points d’appui pour l’expansion de la culture française dans l’immense sous-continent indien.
Keywords: Empire; France; History - Modern / Histoire - Moderne (UMI : 0582); Inde; India; colonies; decolonization; décolonisation

Une confrontation comme nulle autre dans le Pacifique : la France, la Grande-Bretagne et la vie politique au condominium franco-britannique des Nouvelles-Hébrides (1945-1980) - Stech, Zorian (Université de Montréal, 2018)
Les Nouvelles-Hébrides représentent un chapitre oublié du colonialisme européen. Pourtant, entre 1906 et 1980, ce petit archipel d’environ quatre-vingts îles a été gouverné conjointement par la France et la Grande-Bretagne. C’est déjà en soi une grande contradiction : deux nations historiquement opposées ont régi une colonie conjointement dans un siècle connu pour ses rivalités coloniales. Comme le titre de la thèse le suggère, la France et la Grande-Bretagne ne s’entendaient pas sur tous les aspects liés à la gouvernance du condominium franco-britannique des Nouvelles-Hébrides. Même si l’administration conjointe de l’archipel a commencé en 1906, la thèse se concentre sur la période de 1945 à 1980. Cela ne veut pas dire que les événements d’avant 1945 peuvent être ignorés, loin de là. Dans l’introduction et dans le premier chapitre, certains faits remontant à la création du condominium jusqu’à la Seconde Guerre mondiale sont examinés pour mieux comprendre les origines de certains des événements qui jalonnent le chemin vers l’indépendance de l’archipel. Analysant essentiellement les années 1945 à 1970, le premier chapitre souligne l’impact sans précédent que la Seconde Guerre mondiale a eu sur les Nouvelles-Hébrides. Il ne laisse aucun doute qu’aux Nouvelles-Hébrides, les Français et les Britanniques devaient prendre en considération les aspirations et les besoins des peuples mélanésiens. La question foncière et l’aliénation des terres ont été utilisées comme véhicules pour l’affranchissement politique des Mélanésiens. Le lien entre l’éducation et la participation croissante des Mélanésiens dans la vie politique de la colonie est également exploré. Les deuxième et troisième chapitres se concentrent sur une période beaucoup plus restreinte que le premier chapitre (les années 1970 à 1975 pour le deuxième chapitre et les années 1975 à 1977 pour le troisième chapitre). Ces deux chapitres analysent la vie politique aux Nouvelles-Hébrides qui, dans un court laps de temps, a revêtu les caractéristiques d’une démocratie moderne : partis politiques, campagnes électorales et élections. Ils cherchent à éclaircir le rôle et la place de la France et de la Grande-Bretagne sur la scène politique émergente aux Nouvelles-Hébrides. Analysant les années 1978 et 1979, le quatrième chapitre ne laisse plus aucun doute sur le fait que les Nouvelles-Hébrides se dirigeaient vers une indépendance imminente. Il traite en grande partie des dispositions qui furent mises en place pour préparer l’indépendance. Une fois de plus, les positions de la France et de la Grande-Bretagne sont considérées. Finalement, le cinquième chapitre, qui se penche sur l’année 1980, examine les derniers jours du condominium et démontre que l’indépendance n’a pas été obtenue dans la paix, mais plutôt dans le sang. Cette thèse démontre qu’à la veille de l’indépendance des Nouvelles-Hébrides en 1980, les Britanniques avaient l’avantage sur les plans culturel, social et politique par rapport aux Français. Ils exerçaient également une plus grande influence auprès de la population mélanésienne.
Keywords: France; Grande-Bretagne; Great Britain; History - Asia - Australia and Oceania / Histoire - Asie - Australie et Océanie )(UMI : 0332); Melanesians; Mélanésiens; New Hebrides; Nouvelles-Hébrides; Pacific; Pacifique; condominium; decolonization; décolonisation; partis politiques; political parties

La gauche française et la guerre d'Espagne (1936-1939) : entre idéalisme et pragmatisme - Vaillancourt, Johanne (Université de Montréal, 2008)
Keywords: Communism; Communisme; France; Front populaire; Ideology; Idéologie; Journaux; Newspapers; Popular front; Socialism; Socialisme

Le Service d'ordre légionnaire et la Milice de Toulouse-Pyrénées : une étude régionale - Berrardelli, Dominique (Université de Montréal, 2024)
Depuis l’ouverture des archives judiciaires de la Seconde Guerre mondiale en décembre 2015, nous assistons à un renouveau dans les recherches sur la collaboration en France. L’état de la recherche sur la Milice française se compose d’études nationales du mouvement ainsi que des études départementales. Les recherches précédentes sont basées sur les grandes figures de la Milice et leurs actions de répression, ce qui délaisse les adhérents. Depuis les dossiers de justice des SOL et miliciens de la région Toulouse-Pyrénées, nous proposons une recherche prosopographique de la Milice française. Avec ces données, nous abordons plusieurs éléments comme l’histoire sociale de la Milice dans la région, les motivations pour l’adhésion, les différentes vagues de démissions et l’exode du mouvement en août 1944. L’aspect novateur de cette recherche réside dans son cadre d’analyse régional, qui comprend neuf départements. Au terme de notre étude, nous pouvons affirmer que la composition du SOL et celle de la Milice diffèrent beaucoup par leur composition sociale, les motivations idéologiques derrière l’adhésion et l’usage de la répression envers les Français. Nos recherches montrent également qu’il y a des liens entre le SOL et les mouvements locaux de résistance.
Keywords: =CL

Justifier et promouvoir l’empire français par l’archéologie (1880-1914) - Albert, Gabrielle (Université de Montréal, 2025)
Dans les années 1880, la France s’extirpait de dix années de repentance que sa défaite à l’issu de la guerre franco-prussienne en 1871 lui avait imposée. Déterminée à afficher son retour en force aux puissances européennes, elle se relança dans la course aux colonies avec une ardeur inégalée jusqu’à la Première Guerre mondiale. Si le Second Empire ne se préoccupa que très peu de la méfiance et de l’indifférence du public à l’égard de l’empire, les intentions expansionnistes de la Troisième République dépendaient, quant à elles, de l’appui de l’électorat, rendant son soutien, voire son engouement indispensable. Outre un argumentaire économique, une « culture coloniale » s’imbriqua dans les multiples sphères culturelles consommées par les Françaises et les Français. Ce discours veillait à légitimer, promouvoir et familiariser le public aux colonies. Au travers une variété de leviers mobilisés pour mener à bien ces objectifs, l’archéologie en milieu colonial eut une place de choix dans les argumentaires. Profitant de sa maniabilité, sa polyvalence et son aspect tangible, elle agit autant en soutien aux récits légitimateurs glorifiant les empires romain et khmer déchus que comme moyen de promotion impériale. Son caractère mystérieux qui suscite, à ce jour, la curiosité du public, servit à stimuler l’intérêt, mais également le patriotisme des métropolitains. Bien que la place de l’archéologie dans ces argumentaires pro-coloniaux était connue, ce mémoire met en lumière la variété de ses usages qui servirent bien au-delà de la légitimation de la présence française en Afrique du Nord.
Keywords: =CL

Un garde-fou de la démocratie : la conception utilitaire de la religion chez Alexis de Tocqueville (1805-1859) - Bouchard, Carl (Université de Montréal, 1995)

Vichy, la France libre et le Canada de 1940 à 1945 - Trudeau, Samuel (Université de Montréal, 1996)

La question du fascisme français, 1924-1939 : une étude historiographique - Roy, Dominic (Université de Montréal, 1994)

La politique étrangère de la France sous la présidence de Georges Pompidou (1969-1974) - Cordeau, Julie (Université de Montréal, 1995)

L'engagement politique et intellectuel de Jean Guéhenno face aux conflits mondiaux de 1914 à 1945 - Pelletier, Emmanuelle (Université de Montréal, 1997)

La dimension économique de la stratégie française lors du conflit finno-soviétique de l'hiver 1939-1940 - Jean, Christian (Université de Montréal, 1998)

Le plan de Constantine : contexte, objectifs et résultats (1959-1963) - Michon, Sylvie (Université de Montréal, 1997)

La loi du divorce civil d'Alfred Naquet, France (1884): une réforme sociale - Fima, Joseph (Université de Montréal, 1992)

La France, le Proche-Orient et la problématique israélo-palestinienne, 1981-1984 - Vallières, Louis (Université de Montréal, 2025)
Cette thèse d’histoire des relations internationales examine la politique de la France à l’égard du Proche-Orient et de la question israélo-palestinienne entre 1981 et 1984, soit durant les trois premières années de la présidence de François Mitterrand. La problématique centrale cherche à déterminer dans quelle mesure cette politique s’inscrit dans une logique de continuité ou de rupture par rapport aux orientations de ses prédécesseurs, depuis Charles de Gaulle. Cette période constitue un moment clé de la diplomatie française au Proche-Orient, bien que l’historiographie se soit davantage concentrée sur les réformes intérieures du gouvernement socialiste. À travers l’analyse d’un vaste corpus d’archives, cette recherche éclaire les décisions et dynamiques qui ont façonné la politique française face au conflit israélo-palestinien, aux États arabes, aux relations avec les superpuissances ainsi qu’aux interactions avec Israël et les Palestiniens. Les pronostics qui annonçaient un revirement significatif de la politique proche-orientale française après l’élection de François Mitterrand en mai 1981 méritent d’être nuancés. Mitterrand et le Parti socialiste cherchaient à maintenir un équilibre entre leur proximité traditionnelle avec Israël et l’héritage diplomatique gaulliste, caractérisé par de meilleurs rapports avec le monde arabe. Toutefois, cette posture s’est heurtée aux réalités géopolitiques, notamment à la guerre du Liban, aux tensions croissantes avec la Syrie et aux divergences persistantes avec les dirigeants israéliens. Paris a tenté de promouvoir une solution diplomatique à la problématique israélo-palestinienne en encourageant l’OLP à emprunter la voie politique et à rechercher une reconnaissance mutuelle avec Israël, une stratégie qui s’est néanmoins révélée inacceptable pour Washington et Tel Aviv. Si Paris avait initialement affiché une volonté d’indépendance diplomatique, elle a progressivement dû s’aligner sur la stratégie américaine, brouillant ainsi son positionnement traditionnel d’intermédiaire dans la région. Cette période révèle les limites de l’influence française au Proche-Orient. Bien que la France ait cherché à affirmer son statut de puissance indépendante, elle a dû composer avec des contraintes stratégiques qui ont restreint sa marge de manœuvre. Cette thèse met en évidence un équilibre délicat entre l’héritage gaulliste, la préservation des intérêts économiques et la volonté d’adopter une posture active dans la région, tout en ne disposant que de leviers d’action limités sur le terrain.
Keywords: =CL

La décennie 1960 - Saul, Samir (Histoire mondiale des relations internationales : de 1900 à nos jours, 2023)

Le pétrole a-t-il été sanctuarisé durant la guerre d'Algérie? - Saul, Samir (Le pétrole et la guerre : Oil and war, 2012)
Section: 1 vol. (430 p.) : ill., cartes, couv. ill. ; 22 cm.

Le nationalisme arabe, rétrospective et prospective : un essai - Abou-Hsab, Georges; Saul, Samir (Guerres mondiales et conflits contemporains, 2016)
Courant dominant il y a à peine une génération, le nationalisme arabe cède la place à l’islamisme. L’idée nationale, voire l’État-nation semblent avoir fait leur temps. Pourtant l’exercice du pouvoir en Tunisie et en Égypte de 2011 à 2013 s’avère funeste à l’islamisme ; l’échec et le rejet sont d’une rapidité remarquable. Restent entiers les problèmes et défis auxquels il était confronté: lutte pour l’indépendance, l’unité, la modernisation et le développement. Dans la mesure où ils demeurent d’actualité, l’expérience historique du nationalisme arabe ne perd pas sa pertinence. D’où l’intérêt de revisiter cette tentative de réaliser des avancées sur les quatre plans fondamentaux. Le nationalisme arabe a été le vecteur d’une quête de progrès, de modernité et d’émancipation. Il est possible qu’il appartienne définitivement au passé, mais la non-réalisation des aspirations qu’il a incarnées rend toujours concevable sa réactivation.
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0

United States Cultural Policy in France 1945 to 1958 - Bernstein, Martha E. (Université de Montréal, 1999)
Keywords: Histoire

Cavalier seul : la France contre les interventions multilatérales durant la crise congolaise, 1960-1963 - Mukanya, Jean-Bruno; Saul, Samir (Relations internationales, 2010)

La perception des Alliés dans la presse de la Résistance française (1940-1944) - Guérard-Bigras, Laurie (Université de Montréal, 2023)
The French Resistance press was born following the defeat of France and the signing of the armistice with Germany in June 1940. It embodied the will of some French citizens to refuse the occupation and to represent an alternative to Vichy France. In addition to countering official propaganda, the underground newspapers published their vision of the France to be rebuilt in the post-war period. Our master’s thesis analyzes the perception of the Allies in the French Resistance press between 1940 and 1944, in order to highlight the extent to which France's place in the world is visible through the vision shown of the three great powers, who are allies, but who could represent threats after the Liberation. The portraits of the Allies allow us to analyze and understand the plans and concerns of the Resistance. Based on a discursive, diachronic and thematic analysis of the clandestine newspapers, we are able to show that the perception of the Allies evolves during the course of the war, moving from a generally positive view between 1940 and 1942 to a more critical perception in the spring of 1944. At the beginning of the war, the Resistance offered a portrait of the Allies based on their military strength. Nevertheless, from 1943 onwards, it had to protect the population and gain legitimacy. This change strengthened the Resistance and allowed it to gradually impose itself as the authority protecting French interests in the face of Allies whose postwar intentions were increasingly criticized.
Accepted: 2023-05-11T19:53:03Z
Keywords: =CL; Allies; Alliés; European history / Histoire de l’Europe (UMI : 0335); France; Resistance; Resistance press; Résistance intérieure; Seconde Guerre mondiale; World War II; international relations; presse de la Résistance; relations internationales

La controverse entourant la "guerre révolutionnaire" pendant la guerre d'Algérie (1954-1962) - Boivin, Marc André (Université de Montréal, 2001)
Keywords: Histoire

La politique allemande de la France telle que perçue par la presse française (1919-1926) - Chartier Jacques, Christopher (Université de Montréal, 2011)
La France est souvent perçue comme la principale garante du traité de Versailles. Le révisionnisme français envers l’ordre établi par le traité, contrairement au même courant chez les responsables allemands, est un sujet peu étudié. Il a été abordé par quelques auteurs, tels George-Henri Soutou et Stanislas Jeannesson, mais la question mérite davantage d’élaboration. Grâce à l’analyse de la presse française, ce mémoire vérifie l’existence d’une volonté de rendre le traité de paix plus favorable à la France. Une Machtpolitik ainsi qu’un révisionnisme français sont apparents de 1919 à 1923 avec, comme zénith, l’occupation de la Ruhr. Les années suivantes virent la situation de la France se détériorer sur les plans politique, économique et diplomatique. La dégradation de sa posture inclina la France à se tourner vers une conciliation qui émanait de l’esprit du traité de Versailles. La couverture de l’actualité internationale de trois journaux français (Le Temps, L’Action française et L’Humanité) avant et après l’invasion de la Ruhr est analysée. On constate l’existence d’un révisionnisme français qui mène, après son échec en 1924, à un recentrage de la politique allemande de la France. En liant la perception des différents journaux à leur idéologie, nous avons aussi expliqué les variations dans leurs analyses des mêmes événements. L’étude de la presse, conjuguée aux sources secondaires, révèle un discours teinté d’une volonté révisionniste. Elle porte à croire, aussi, que le traité de Versailles ne fut réellement défendu en France qu’après l’échec de la politique de puissance et du révisionnisme français.
Keywords: France’s newspapers; French revisionism; History - European / Histoire - Européenne (UMI : 0335); Occupation de la Ruhr; Occupation of the Ruhr; Raymond Poincaré; Treaty of Versailles; collective security; franco-german diplomacy; presse française; rapports franco-allemands; révisionnisme français; sécurité collective; traité de Versailles

L'industrie française en Indochine de 1897 à 1945 - Dang Van, Chuong (Université de Montréal, 2000)
Keywords: Histoire

La mode française : vecteur d'influence aux États-Unis de l'après-guerre à l'orée des années 1960 - Dubé-Senécal, Vincent (Université de Montréal, 2019)
This thesis is a survey of a rarely studied field of international relations. It is interested in the role of women’s sartorial fashion within the Franco-American postwar relations between 1946 and 1960. The analysis takes on the French perspective through the prism of the public authorities and diplomatic bodies, Parisian couturiers, and textile manufacturers. This orientation highlights the two fields on which these actors wish to see manifest an influence of fashion in the United States, namely commercial and prestige propaganda. In their perspective, these two forms of propaganda can be implemented either through indirect actions (press coverage of their fashion shows) or direct actions (shows organized to promote specific products or French production as a whole). The analysis is then completed by integrating the perspective of American fashion professionals (specialized press, manufacturers and retailers) and that of the American diplomatic bodies in France, and the study of customs statistics in order to evaluate, from the viewpoint of these historical actors, the degree of success of fashion as an instrument of French influence in the United States in regard of the initial French expectations. The research question answered by this thesis is: How important is fashion as an instrument of French influence in the United States after the Second World War? In order to answer it, the analyses procedes in three steps. On the one hand, the intersection of the historical contexts of fashion and Franco-American relations highlights the importance of the advent of the American superpower. This requires the French to adapt in terms of their production methods and their relationship to the American perspective of liberal and democratic modernity. On the other hand, the research was based on a chronological approach distinguishing between the 1946-51 and 1952-60 periods. The first one precedes the state intervention in favor of the Parisian couturiers and the second one is dominated by the state-sponsored Aid to Parisian couture. The thesis shows that the commercial influence of Parisian fashion in the United States did not materialize contrary to the couturiers’ claims and to the textile industrialists’ expectations. However, with respect to its influence through prestige propaganda, the situation is quite different. Long regarded as an ersatz to the commercial purpose of propaganda by the state – with the exception of the French diplomatic bodies that particularly appreciate its prestige purpose –, from 1957, France’s “rayonnement” through the dissemination of fashion ideas becomes key to French leaders. From then on, its role is to take advantage of the craving for Parisian fashion ideas to ensure a French presence – beyond fashion – in the American market: a mass market otherwise difficult to penetrate, being the largest in the world.
Keywords: Commercial relations; Fashion; France; Haute couture; History - European / Histoire - Européenne (UMI : 0335); Influence transnationale; International relations; Mode; Propaganda; Propagande; Relations commerciales; Relations internationales; Transnational influence; United States; États-Unis

Europe et identité nationale française : d’un référendum à l’autre, 1992-2005 - Dubé-Senécal, Vincent (Université de Montréal, 2014)
The European project, through each of its milestones, outlines a new type of entity on the international scene, one which is a stranger to the nation state without being its better. From the intensification of European integration emerged a questioning on the nature of the interactions between national and European identity. In this respect, France represents a very interesting field of study as the country organised two referendums on European integration, one in 1992 and the other in 2005. The main goal of this research is to reveal the way in which the construction of a national discourse within the French public opinion is influenced by the deepening of European integration. The analysis covers both debate periods before the 1992 and 2005 referendums dealing with the ratification of the Maastricht Treaty on the Euro and the Treaty establishing a Constitution for Europe. This work is based on a press analysis covering both periods of debate. In order to study the evolution of the French perception of their national identity with the least political bias possible, this thesis relies on documentary resources comprising editorials and letters to the editor of four newspapers: Le Monde, Le Figaro, L’Humanité and Libération. The comparison of the identity discourses of 1992 and 2005 reveals that the relation of identification between France and Europe has drastically changed during this period. It went from a relation founded on alterity to a relation founded on shared values. In 1992, the French use the European idea as an identity referent around which they reaffirm the “frenchness” of their shared values. In 2005, the French national identity is not in question anymore. From now on, the debate turns around the values the French hope to see at the root of the European identity to which they are called to adhere. These values are henceforth drawn from the personal identity of each Frenchman rather than from an encompassing concept of the French national identity.
Keywords: Constitution européenne; European Constitution; France; History - European / Histoire - Européenne (UMI : 0335); Identité nationale; Maastricht; National identity; Referendums; Référendums

L'expédition de la France au Liban sous Napoléon III (1860-1861) - Fortin-Gagné, Valérie (Université de Montréal, 2016)
Throughout the nineteenth century, the Ottoman Empire grew weaker and seemed headed for collapse. It became the object of the ambitions and rivalries of the European powers. Under its suzerainty, Syria, including the Mount Lebanon region, was a key area strategically since it dominated the access routes to India and southern and eastern Asia. France and England both tried to impose their influence by way of local communities. France acted through the Christian Maronites, while Britain used the Druzes. In the spring of 1860, trouble broke out between the two communities, resulting in the massacre of thousands of Christians. The European powers, at the behest of the government of Napoleon III, agreed to intervene by sending a commission of inquiry and troops. The expedition’s official mission was to help the Ottoman Empire to restore order and to protect Christians. This thesis shows that imperial France pursued political and economic goals with regard to Syria and Lebanon. The historiography had not previously analyzed in depth the real French mobile in this expedition. The political and economic ambitions were far more important in its decision to set in motion an expedition than the "humanitarian" Christian duty of providing protection or the satisfaction of the public opinion. Far from being deterred by the catastrophe of the massacre that threatened the survival of its protégés and therefore its influence in Syria, Paris, and especially its foreign minister E. Thouvenel, managed to turn the situation to his advantage. Skilfully using the desire of interference of other powers and its role as protector of Christians, France managed to corner England, which opposed the intervention, and justify it on principles far removed from its real objectives. The troubles finally represented for her an opportunity to widen the autonomy of the Mountain vis-à-vis the central authority of the Ottoman Empire and to increase the economic and political power of its clients through the revision of the administrative status of the region. In so doing, it has strengthened its influence in the eastern Mediterranean and moved a step closer to dominating Syria.
Keywords: Empire ottoman; France; History - European / Histoire - Européenne (UMI : 0335); Lebanon; Liban; Maronites; Napoleon III; Napoléon III; Ottoman Empire

L'image du régime Ceausescu dans la presse française : étude de cas dans trois quotidiens : Le Monde, Le Figaro et L'Humanité (1965-1989) - Grigore, Anamaria Monica (Université de Montréal, 2008)

Les mutations socio-économiques de la Corse de 1957 à nos jours - Lucia, Virginie de (Université de Montréal, 2004)
Keywords: Amélioration; Changements administratifs et politiques; Condition de vie; Corse; Développement économique; Mutations; Secteurs d'activité

L'infanterie dans la doctrine militaire française des années trente - Lussier, Jean-François (Université de Montréal, 2000)
Keywords: Histoire

La presse française et l’adhésion de la Grande-Bretagne à la CEE : des refus à l’acceptation (1961-1973) - Morin-Gagnon, Renaud (Université de Montréal, 2015)
À la suite de la Seconde Guerre mondiale, l’Europe est affaiblie et divisée. Les horreurs de la guerre amènent les Européens à repenser leur cohabitation et l’idée d’une Europe, unie par des liens économiques et politiques forts, germe dans l’esprit des Européens. Ils créent alors la CECA en 1951 puis, sept ans plus tard, la Communauté économique européenne. Puisque cette dernière aura du succès, certains pays européens, dont la Grande-Bretagne, demandent à la rejoindre. La France d’alors, sous la présidence de Charles de Gaulle, s’oppose à cette demande d’adhésion à deux reprises, en 1963 et en 1967. Il faut attendre l’arrivée de Georges Pompidou à l’Élysée pour que Londres intègre la CEE. L’élargissement de la Communauté est un évènement important; il a un impact direct sur le rôle de la France en Europe et dans le monde. Il a également une incidence certaine sur le rôle de l’Europe dans le monde bipolaire de l’époque, ainsi que sur ses relations avec l’allié américain. La presse des pays concernés suivra ces évènements avec intérêt, telle la presse quotidienne française, qui commente abondamment les décisions prises par son gouvernement. Le présent mémoire, qui étudie certains journaux d’importance à la lumière des ouvrages d’érudition et des sources primaires, analyse thématiquement la position de journaux français de diverses tendances politiques sur la politique française au cours des trois demandes.
Keywords: Communauté économique européenne (CEE); European Economic Community (EEC); Fifth Republic; Grande-Bretagne; Great Britain; History - European / Histoire - Européenne (UMI : 0335); Ve République; press; presse; widening; élargissement

L’indépendance à tout prix : la Belgique face à la France durant l’Entre-deux-guerres - Pelletier Deslauriers, Kevin (Université de Montréal, 2018)
Cette étude s’intéresse à la dynamique des relations franco-belges durant l’Entre-deux-guerres. L’objectif est de définir si la Belgique a été un satellite de la France pendant la durée de l’accord militaire franco-belge de 1920. Utilisant les archives diplomatiques du ministère des Affaires étrangères belge, l’étude démontre que la Belgique, alors même qu’elle tente de maintenir une harmonie entre les membres de l’Entente (Angleterre, France, Belgique), agit dans son plus pur intérêt national. Ainsi, alors que les évènements majeurs de l’Entre-deux-guerres se déroulent -occupation de la Ruhr, signature du Traité de Locarno, démilitarisation de la Ruhr et l’élection d’Hitler- la Belgique démontre qu’elle est une actrice indépendante et importante dans l’évolution de la diplomatie européenne. La rupture de l’accord militaire franco-belge en 1936 est généralement perçue comme une rupture des relations diplomatiques entre les deux pays alors qu’elle ne représente que la volonté belge de ne pas être entrainée dans une guerre qui ne la concerne pas. Ainsi, la présente étude cherche à clarifier la relation franco-belge. Elle démontre que les interactions entre la Belgique et sa grande voisine n’ont rien d’une relation de subordination.
Keywords: Belgique; Belgium; Diplomacy; Entre-deux-guerres; France; Histoire des relations internationales; History - European / Histoire - Européenne (UMI : 0335); Independence; Indépendance; International relationship history; International relationships; Interwar period; National Security; Relations internationales; Sécurité nationale

L’internationalisme socialiste français et allemand devant la montée de l’impérialisme (1896-1912) - Soucy, Louis-Félix (Université de Montréal, 2022)
The rise of the European socialist movement under the leadership of the Second International at the turn of the century and its breakup with the outbreak of the 1914 war is a persistent historical problem. The contradiction is obvious. Here was a movement that firmly proclaimed "proletarian internationalism", but which, when the time came to implement it, affirmed the necessity of "national defense". The concrete forms of this contradiction are illuminated by a study of the impact of the rise of imperialism on the internationalism of French and German socialists in the period leading up to the war, from the London Congress of 1896 to the resolution of the Agadir crisis in 1912. The Second International is a movement whose organizational and practical forms are rooted in a national framework, while its fundamental conceptions are those of internationalism. Imperialism reinforces this contradiction, and becomes at the same time the source of a concretization of socialist internationalism in theory, and of its abandonment in practice. Emphasizing the analysis of internationalism as a political rather than a cultural or sentimental phenomenon, this work demonstrates the existence of a chasm between the theoretical discourse and the practice of the movement. The rise of imperialism is accompanied by the rise of reformism within the socialist movement, which, along with other phenomena, reinforces its national tendencies. The national tendencies of the movement persisted at key moments, notably the imperialist crises of Tangier (1905) and Agadir (1911), to the point of calling into question the internationalist foundations of the movement.
Keywords: Modern history / Histoire moderne (UMI : 0582); crises; imperialism; impérialisme; international; internationale; internationalism; internationalisme; marxism; marxisme; reformism; réformisme; social-democracy; social-démocratie; socialism; socialisme

L'attitude des journaux français face au conflit libanais 1975-1990 - Warren, Marie-Pierre (Université de Montréal, 1998)
Keywords: Histoire

Affronter le nationalisme : la France en Syrie à l’époque du Mandat (1918-1946) - Abou-Hsab, Georges (Université de Montréal, 2024)
Résumé : Ni une narration chronologique, ni une exploration détaillée d'un ou de quelques événements, cette thèse aborde l'ensemble de la période mandataire d'un angle particulier, celui de la réponse française au nationalisme arabe en Syrie telle que révélée dans les archives et autres sources françaises. Elle s'intéresse aux mécanismes de pensée par lesquels une pionnière de l'idée nationale s'est trouvée à combattre cette idée chez un autre peuple. Le Mandat accordé par la Société des nations a pour but déclaré d'accompagner les sociétés nouvellement libérées de l'occupation ottomane sur le chemin de la maturité politique complète et, donc, de l'indépendance. Utilisant ce cadre juridique qu'elle a elle-même mis en place de concert avec la Grande-Bretagne et d'autres vainqueurs de la Première Guerre mondiale, la France occupe la Syrie et le Liban entre 1920 et 1946 et administre jusqu'en 1943 leur vie politique, leurs finances et leur économie. Or, ne ré-pondant ni au texte ni à l'esprit du Mandat, ses agissements soulèvent des interrogations sur les vrais objectifs. Cette thèse propose une réponse en montrant que le but ultime de la France est d'assurer une position dominante pérenne au Levant, militairement, culturellement et politiquement, et qu'elle conçoit le Mandat comme une mainmise coloniale, adoucie, peut-être, mais aucunement différente dans son essence des autres conquêtes coloniales entreprises dès le XIXe siècle. Un obstacle majeur se dresse toutefois contre l'ambition française : le nationalisme des Syriens. La thèse fait état des méthodes utilisées pour mettre au pas le mouvement nationaliste. La France qualifie la Syrie d'agglomération de communautés, une antithèse du concept de nation. Elle entame son Mandat par une division du pays en plusieurs petits États, une division qu'elle finit par abandonner en 1936 au prix de luttes politiques et de révoltes sanglantes, sans toutefois renoncer à sa perception irrémédiablement communautariste de la population syrienne. En plus de la division politique, les manipulations de l'économie, des finances et des classes sociales font partie de l'arsenal exploré dans la thèse, de même que les méthodes militaires et policières ininterrompues tout au long du Mandat, quoique avec une intensité variable. La thèse attribue l'échec, que l'on constate inévitable, de la France à réaliser aucune de ses ambitions à des idées préconçues sur la région, au refus de prendre en compte les réalités et à une intransigeance condescendante dans les relations avec les Syriens.
Accepted: 2024-06-18T15:42:06Z
Keywords: =CL

Défense et sécurité dans les relations franco-allemandes de 1982 à 1990 - Jacques, Maurice A (Université de Montréal, 1995)

Une comparaison entre l’utilisation des troupes africaines par la France et l’Allemagne pendant la Première Guerre mondiale - Buitron Trindade, Marco Antonio (Université de Montréal, 2014)
Pendant la Première Guerre mondiale, les puissances occidentales étaient obligées d’utiliser toutes leurs ressources afin de vaincre. Dans les colonies allemandes, les troupes coloniales, la Schutztruppe, la plupart étant des Africains noirs, avaient la responsabilité de défendre les colonies contre tout envahisseur. Pour sa part, la France craignait, depuis la fin de la guerre franco-allemande, l’écart démographique vis-à-vis de l’Allemagne. Elle a finalement pris la décision de renforcer ses troupes par des soldats africains, les Tirailleurs sénégalais étant les plus nombreux. Ce mémoire vise à analyser et à comparer le recrutement et le déploiement dans les deux cas, particulièrement l’idéologie qui soutenait ce recrutement, les relations entre Africains et Européens pendant la guerre, la contribution des Africains à l’effort de guerre, ainsi que les conséquences de la visibilité accrue des Africains dans la société européenne. En général, nous pouvons remarquer d’importantes ressemblances entre les deux cas, en particulier le fait que l’utilisation de troupes coloniales a eu pour fonction de justifier leurs politiques coloniales et de condamner celles de leur adversaire.
Keywords: Allemagne; Askari; First World War; France; Germany; History - European / Histoire - Européenne (UMI : 0335); Première guerre mondiale; Tirailleurs

La nazification de l'Allemagne perçue à travers la presse alsacienne francophone (1933-1939) - Durand St-Georges, Caroline (Université de Montréal, 2015)
At the dawn of 1930s, Alsace shares a troubled past with France and Germany. While the region came again under French rule after the First World War in 1919, Paris has difficulty integrating Alsace in the Republic, because it does not understand that forty years of German control upset the region's life at the political, cultural, religious and linguistic levels. France does not perceive the sense of identity of the population and its will to preserve its values. The Alsatian separatism of the 1920s and the repression of the movement by the French authorities damage the relations between Paris and Strasbourg. Along with the tension of the 1930s, Adolf Hitler's arrival to power in 1933 in Germany radically modified the situation. The thesis examines how the French-speaking Alsatian press perceived the rise of Nazism in Germany from 1933 to 1939. Did Alsace question its allegiance to France, a country that demonstrated signs of weaknesses, and did not clearly understand Alsace? Or did it prefer a strong and stable Germany? By consulting newspapers of various political and religious orientations, such as Les dernières nouvelles de Strasbourg, Le nouvelliste d'Alsace, Le Lorrain et L'éclair de l'Est, the thesis analyzes the opinion of the Alsatian press on the German events in the 1930s. The French-speaking press was not in favour returning to the Reich. Nevertheless, the allegiance to France was not as clear as the historiography leads us to believe on this matter. Until March 1938, the French-speaking Alsatian press did not claim particular status, even if it was dissatisfied with the options available, as much on the side of France as on the side of Germany. The region's point of view changed regularly. While Hitler caught everyone's attention in 1933, the unstable political situation in France as well as the choices of the Popular Front are the target for the French-speaking Alsatian press from 1936. It was only when the war seemed inevitable that it lined up behind the French Republic.
Keywords: Allemagne; Alsace; France; Germany; History - European / Histoire - Européenne (UMI : 0335); nazism; nazisme; press; presse

Nationalisme, construction nationale et «action extérieure» : les entités nationales non souveraines espagnoles et l’Union européenne (1992-2008) - Ionita, Ovidiu Cristian V. (Université de Montréal, 2014)
Cette thèse porte sur l’évolution des relations des « nationalités historiques » espagnoles avec l’Union européenne dans les années 1992-2008. L’analyse se concentre sur la genèse d’une paradiplomatie nationaliste européenne dont l’objectif est la reconnaissance de l’identité nationale de ces communautés au sein de l’Union européenne. Après avoir obtenu une certaine reconnaissance nationale et un statut privilégié en Espagne, les élites de ces « nations sans État » ont remarqué que le processus de construction de l’Union européenne a des conséquences négatives sur leur autonomie et, dans ce contexte, ces élites nationalistes sont obligées à concevoir une vraie politique européenne pour protéger leurs intérêts nationaux en Espagne et dans l’Union européenne. À partir de l’étude des rapports établis entre les « nationalités historiques » espagnoles avec l’Union européenne, nous démontrons que l’involution autonomique (en Espagne) et le manque d’empathie de l’Union européenne envers ces communautés nationales sont les principales causes de la genèse de leur politique européenne. Loin d’être simplement associée à une forme de régionalisme ou de néo-régionalisme, cette politique étrangère (« action extérieure ») de ces entités envers l’Union européenne fait partie d’un processus de construction nationale et pourrait être définie comme une paradiplomatie nationaliste. La présente thèse, basée sur une analyse de la politique européenne des « nationalités historiques » entre 1992 et 2008, soutient que les limites du dessein institutionnel de l’Union européenne représentent la principale raison d’être de l’évolution de la paradiplomatie nationaliste vers une protodiplomatie apparemment incohérente. Dans une telle situation, l’inaptitude institutionnelle de l’Union européenne à accommoder les demandes nationalistes serait une cause majeure de l’échec des initiatives nationalistes autonomistes et, en même temps, une cause de l’émergence d’un nouveau courant nationaliste au sein des élites des « nations sans État » occidentales, dont le but est la construction d’un propre État national à l’intérieur de l’Union européenne.
Keywords: Autonomie; Autonomy; Espagne; European Union; Foreign Affairs; History - European / Histoire - Européenne (UMI : 0335); Nation sans État; Nation without State; Nationalism; Nationalisme; Nationalist Paradiplomacy; Paradiplomatie nationaliste; Politique étrangère; Regionalism; Régionalisme; Spain; Union européenne

La politique française en Afrique centrale de 1990 à nos jours - Kabeya, Mudi Wa Mbuji (Université de Montréal, 2008)

Harnessing Americanisation: the case of the Zellidja Mining Company - Saul, Samir (Americanisation in 20th Century Europe: business, culture, politics. Volume 2, 2018)

Imperial Banking in North Africa : Banque de l’Algérie et de la Tunisie (1851-1963) - Saul, Samir (Colonial and imperial banking history, 2016)

Colonial banking in French North Africa: Banque de l'Algérie et de la Tunisie (1851–1963) - Saul, Samir (Colonial and Imperial Banking History, 2015)
Colonial banking in French North Africa - 1 - Banque de l'Algérie et de la Tunisie (1851–1963)
Num Pages: 33

L'opposition du PCF et du PCI au bloc atlantique : entre politique intérieure et enjeux internationaux (1947-1955) - Sollai, Luca (Université de Montréal, 2023)
This thesis studies the opposition of the Italian Communist Party (ICP) and the French Communist Party (FCP) to the Atlantic bloc, from the beginning of the Cold War until the entry of the Federal Republic of Germany (FRG) into NATO. The approach chosen is to integrate the 'national' and 'international' spheres, in order to avoid framing the analysis solely in terms of Cold War opposition. The comprehension of the oppositional strategies of two parties to the Atlantic bloc is very important, as the PCF and the PCI were the two largest communist parties in Western Europe at the time, and favorable to the French and Italian constitutions after World War II. Considering the interaction between national issues and international pressures, the dissertation draws a portrait of the evolution of the CPF/CPI in their opposition to the Atlantic bloc, highlighting similarities and differences. The thesis relies on several primary sources, such as official documents of the two parties and Italian, French, Russian and American diplomatic and ministerial documents, to explain the evolution of the two parties. While the starting conditions, with the exclusion from the national governments of both parties and the increased pressure from the US and the Soviet Union were similar, the long-term development of strategies was different. In general, the PCF was more "dogmatic", in relation to the Atlantic bloc. Consequently, the tendency of the French communists was to focus more on the international situation than on national issues, with a reversal of this tendency only in the mid-1950s, during the campaign against the EDC. For their part, the Italian communists were able, from the start and notwithstanding international pressures, to develop a more balanced opposition taking into account national issues and the international situation. As a result, the PCI's strategy was more effective, as it repeatedly challenged the Italian government on its Atlantic choice.
Accepted: 2023-11-23T16:58:08Z
Keywords: =CL; Anti-Atlantism; Antiatlantisme; Atlantic Pact; Cold War; Cominform; Communism; Communisme; European history / Histoire de l’Europe (UMI : 0335); France; French Communist Party; Guerre froide; Italian Communist Party; Italie; Italy; Kominform; NATO; OTAN; PCF; PCI; Pacte Atlantique

L'Afrique occidentale française entre le franc CFA et le projet de développement économique et social depuis 1960 - Abalo, Komi (Université de Montréal, 2024)
This thesis is part of the contemporary history of French-speaking West Africa. Its anchor point is the theme of the CFA franc (Franc of the French community of Africa for West Africa, and Franc of the French cooperation of Africa for Central Africa) and the economic and social development project since 1960. The research is based on a multidisciplinary approach. It analyses the trade and economic policy issues that are constantly being debated at international level. The research focuses on the role of money in international relations: the case of the CFA franc between France and its former colonies in sub-Saharan Africa. For a country, independence means, above all, political, economic and social sovereignty. The CFA franc is a highly topical issue, and one that fascinates many people. In the 21st century, the CFA franc remains the only colonial currency still used by fourteen countries, twelve of which are former French colonies. These are Benin, Burkina Faso, Central African Republic, Chad, Côte d'Ivoire, Congo, Gabon, Mali, Niger, Senegal and Togo. Equatorial Guinea (Spanish-speaking) and Guinea-Bissau (Portuguese-speaking) joined these French-speaking countries in 1984 and 1997 respectively. Faced with the development challenges of today's world, the countries that use the CFA franc are among the bottom of the class. Apart from the high rate of impoverishment, the populations of these countries are subject to the scourges of insecurity (in the Sahel and the Gulf of Guinea, for example) and emigration. Our approach has enabled us to gain a better understanding of how this currency works and its impact on the daily lives of its users.
Accepted: 2024-03-19T13:04:12Z
Keywords: =CL; Africa; African studies / Études africaines (UMI : 0293); Afrique; CFA Franc; Development; Développement; Economy; Franc CFA; France; Politics; Politique; Social; Économie

La presse nationale française et la remise en question du traité de Versailles par l’Allemagne (1933-1939) - Boulanger, Xavier (Université de Montréal, 2022)
During the 1930s, France was hit by a political, economic, and diplomatic crisis which revealed many divisions in society. French journalists, seeking a solution to the national crisis, showed a particular interest towards their neighbor across the Rhine after the nomination of Hitler as Chancellor of Germany on January 30th, 1933. Hitler took advantage of France’s weakness and divisions to question but also oppose and act against the clauses of the Treaty of Versailles until the outbreak of World War II on September 1st, 1939. The objective of this research is to analyze how the French national press reacted to German revisionism from 1933 to 1939. In this context, the press’ perception of Hitler’s actions and how its opinions changed (or not) over time reveals the ways in which French newspapers interpreted events in Germany that affected France itself. By consulting editorials and opinion articles from five daily newspapers of different political orientations, namely L’Action française, L’Humanité, Le Figaro, Le Petit Parisien and Le Temps, this memoire analyse the opinion of the French national press on the revision of the Treaty of Versailles. This study contributes to the historiography of the interwar period and France’s reaction to German aggression in two ways. First, it shows that the press was not blind to Hitler’s revisionist plan. It also demonstrates that the French press remained divided concerning the actions of Nazi Germany until 1939. The protection of the Treaty of Versailles’ clauses and its system, which maintained the balance of power in Europe, polarised the French press and created a weakened national feeling until the outbreak of World War II. German revisionism fuelled the disagreements in the daily newspapers studied from 1933 to 1939.
Keywords: 1933-1939; French national press; German revisionism; History - European / Histoire - Européenne (UMI : 0335); Le Figaro; Le Petit Parisien; Le Temps; L’Action française; L’Humanité; Treaty of Versailles; franco-german diplomacy; presse nationale française; rapports franco-allemands; révisionnisme allemand; traité de Versailles

Influence et usage de la mémoire dans la vision officielle française de l’Allemagne réunifiée (1989-1995) - Giroux, Geneviève (Université de Montréal, 2011)
Ce mémoire part du constat que l’histoire et, a fortiori, la mémoire ont été largement sollicitées par le discours officiel français au moment et au lendemain de la réunification allemande. La fin définitive de l’après-guerre et le retour à la souveraineté diplomatique de l’Allemagne suscitent en France des questions qui inquiètent – en raison notamment du souvenir de l’histoire – et raniment la volonté d’encadrer la puissance allemande dans la communauté européenne. Pour comprendre le rôle que la mémoire a pu tenir dans la diplomatie française, l’étude tente d’analyser l’usage que les responsables français ont fait du passé en tant qu’instrument de la politique étrangère et le poids qu’il a représenté dans la vision française de l’unification allemande. Ce mémoire démontre que l’entendement du passé se conforme, sous toutes ses expressions, à la politique européenne de la France. Il atteste également que la France se saisit de ce moment charnière pour structurer un espace européen qui fait écho aux principes universalistes issus de la Révolution française, lesquels doivent être désormais portés par le binôme franco-allemand. L’invention de la tradition et l’usage métaphorique du passé répondent d’une préoccupation politique de réconciliation franco-allemande et accompagnent la mise en place d’un patriotisme historique sur lequel pourront s’établir les identités civique et juridique européennes. La mémoire officielle, qui est entièrement orientée vers la promotion et la justification de l’avenir communautaire, dénature certaines données historiques de manière à exorciser le présent d’un passé encombrant. Les limites de la mémoire officielle se trouvent donc dans cette représentation d’un passé aseptisé; un passé n’étant pas une finalité, mais un moyen déférant à l’intérêt national.
Keywords: Allemagne; European identity; Foreign policy; France; German Reunification; Germany; History - European / Histoire - Européenne (UMI : 0335); Identité européene; Identité nationale; International relations; Mémoire officielle; National identity; Official memory; Politique étrangère; Relations internationales; Réunification allemande

Peuple de l'ombre, peuple universel : les résistants et les anciens résistants français face à l'Empire et la décolonisation (1940-1962) - Houle, Vincent (Université de Montréal, 2022)
This thesis examines French resistants and ex-resistants’ ties with the Empire, during and after the Second World War. It therefore explores a broader timeframe and geographic area than what previous historiography about French Resistance has offered up until now. In analyzing French Resistance newspapers and constitutional projects from 1940 through 1944, the thesis reveals that while the principles of the Third Republic were repudiated by French society at the time, one particular element remained: the idea of the civilizing mission. Then, through the study of numerous personal testimonies covering the years between the Liberation and the end of the Algerian War, the research offers a profound and nuanced insight on ex-resistants views of the Empire and their point of view on their country's colonial system. After 1944, the power dynamic shifted to the resistants: they were no longer dominated by a violent German state, they were now the ones enforcing domination to the colonies. The testimonies reveal the internal conflict French ex-resistants were dealing with when faced with the problems of decolonization. It also shows how the principles, for which they risked their lives during the war, were modified or reshaped to fit with their views on how to deal with the colonies’ wishes for emancipation. In examining how the war against fascism and the Vichy regime impacted personal attitudes towards the Empire and the exercise of domination, the study offers a new perspective on the French Resistance and French Imperial history from 1940 to 1962, one that accounts for political and economic imperatives as well as for the importance of the different interpretations of the Republic's core principles for these individuals. The individuals were selected because of the importance of their political, social or military commitments through the period. By focusing on the relationships between these successive commitments, the analysis enlarges the scope through which the French Resistance must be understood.
Keywords: Algeria; Algérie; Decolonization; Deuxième Guerre mondiale; Décolonisation; Empire français; European history / Histoire de l’Europe (UMI : 0335); France; French Empire; French Resistance; Imperialism; Impérialisme; Indochina; Indochine; Republicanism; Républicanisme; Résistance française; Second World War; Universalism; Universalisme

Ernest Mercier, le pétrole et la France - Pelletier, François (Université de Montréal, 2016)
Ernest Mercier est l’un des patrons les plus influents de l'entre-deux-guerres en France. Ses différentes activités industrielles l'ont conduit à siéger sur de vastes pans de l’économie française, notamment du secteur énergétique. La thèse retrace la carrière pétrolière d'un homme qui a joué un rôle central pour le développement d'une industrie devenue stratégique, mais qui est embryonnaire lorsqu'il rejoint ce secteur après la Première Guerre mondiale. Mercier assiste et assure la création d'une industrie pétrolière nationale. Les obstacles se font légion contre les ambitions pétrolières de la France. Elle se présente bien tard sur un marché étroitement contrôlé par de puissants trusts. La recherche et l'exploitation pétrolière demandent d'importantes ressources, et aucune société française n'a les moyens d'une politique indépendante. Certaines banques se lancent alors dans les affaires de pétrole en s'alliant aux grands trusts internationaux. C'est le cas de Paribas; la gestion de ses avoirs roumains représente la première expérience de Mercier dans ce secteur. L'État s'intéresse aussi au pétrole, il devient un acteur incontournable. Le gouvernement français n'a pourtant pas les moyens de ses ambitions dans le domaine pétrolier. La politique nationale mise en place durant l'entre-deux-guerres doit faire appel à l'épargne privée française. La création d'une compagnie nationale, la Compagnie française des pétroles, en 1924 regroupe ainsi les différentes banques et sociétés intéressées au pétrole. Mercier est personnellement choisi par le président Raymond Poincaré pour mener à bien cette mission. Cette carrière s'articule donc autour d'un fragile équilibre entre milieux privés et gouvernement. Mercier devient rapidement l'intermédiaire incontournable qui régit ces relations. La thèse s'appuie sur les archives bancaires et industrielles, mais aussi sur celles du gouvernement français et de ses différents ministères. Cette analyse de la carrière d'Ernest Mercier permet de retracer les origines du secteur pétrolier français et l'action déterminante d'un homme. Elle expose les mécanismes d'influence d'une puissante banque d'affaires et les conflits d'intérêts qu'engendre l'exploitation pétrolière.
Keywords: Ernest Mercier; France; History - European / Histoire - Européenne (UMI : 0335); entre-deux-guerres; international relations; interwar; oil; pétrole; relations internationales

Saint-Maron : une paroisse diasporique : église et fidèles maronites à Montréal (1969-2015) - Zakhia, Frederic (Université de Montréal, 2016)
L’immigration maronite à Montréal date de la fin du XIXe siècle, mais c’est dans les années 1970 et 1990, à la suite des guerres au Liban, qu’il y a eu les plus grandes vagues. De rite syriaque antiochien, mais d’obédience catholique romaine, les immigrants maronites n’avaient pas d’église paroissiale propre. Les autorités diocésaines montréalaises avaient rassemblé les catholiques orientaux dans une même église dont le service était assuré par l’ordre melkite du Saint-Sauveur. En 1969, le père de l’ordre maronite mariamite Élias Najjar fonde avec des Égyptiens maronites la première paroisse. Cette étude se penche sur le processus qui a mené à la naissance de cette paroisse, son évolution à travers le temps et la vie de ses paroissiens. L’approche est narrative et descriptive, elle s’inscrit dans le cadre de l’histoire sociale et religieuse. Les résultats de l’analyse mettent en lumière une église nationale et un nouveau modèle de paroisse diasporique, différent du modèle classique, recelant des diversités infranationale, internationale et interconfessionnelle.
Keywords: Canada; Diaspora; History - Church / Histoire - Église (UMI : 0330); Immigration; Maronite Church; Maronites; Montreal; Montréal; Parish; Paroisse; Saint Maron; Église maronite

La démodernisation en marche - Rabilotta, Alberto; Rabkin, Yakov; Saul, Samir (Revue internationale et stratégique, 2013)
En ex-URSS, mais également dans d’autres régions du monde, on assiste depuis la fin de la guerre froide à un phénomène de « démodernisation », caractérisé par une régression généralisée et le retour à des modes d’existence primitifs, ou tout au moins plus anciens. Si la compétition Est-Ouest et les Trente Glorieuses ont favorisé modernisation et mesures progressistes, la primauté de l’ordre néolibéral au-delà de toute alternative entraîne une offensive contre les acquis sociaux et une contestation du droit de certaines nations à se moderniser, mettant en relief l’aspect réversible de la modernité.

La stratégie du groupe sucrier français Say en Egypte (1897-1905): un essai précoce d'industrialisation pour l'exportation? - Saul, Samir (Industrialisation, communication et rapports sociaux en Turquie et en Mediterranee orientale, 1994)
OCLC: 1378197303

Économie: marchés et commerce extérieur - Saul, Samir (La turquie entre trois mondes, 1998)
Purchase online the PDF of La turquie entre trois mondes, Kançal, Salgur,Thobie, Jacques - L'Harmattan - E-book
Publisher: L'Harmattan

La crise économique internationale de 2008 a-t-elle favorisé l’avènement du ‘printemps’ arabe en Égypte ? - Saul, Samir (Crise et mise en crise. Actes du colloque de l'ACSALF 2012, 2015)

Projets citoyens pour une paix durable, en France, en Grande-Bretagne et aux États-Unis (1914-1924) - Bouchard, Carl (Université de Montréal, 2004)
Keywords: Ordre mondial; Pacifisme; Paix durable; Première Guerre mondiale; Relations internationales; Société des nations

Les États-Unis face à la francophonie : les stratégies américaines en Afrique francophone, 1960-1970 - Lefèvre, Marine (Université de Montréal, 2005)
Keywords: Afrique de l'Ouest; Canada; Congo-Kinshasa; Coopération; France; Guerre froide; Organisations internationales/régionales; Québec; Relations internationales; Tunisie

La COFACE entre boom et décélération économique (1966-1985) - Saul, Samir (Explorer les archives et écrire l'Histoire. Autour de Roger Nougaret, 2022)

Maghreb: Naturalizing Insurance in Algeria, Morocco, and Tunisia - Saul, Samir (World insurance the evolution of a global risk network, 2012)
Section: 1 vol. (XVI-729 p.) : ill. ; 26 cm

L'électricité, enjeu de guerre - Saul, Samir (L'ère électrique. The Electric Age, 2017)
The scientific discovery and mastery of electricity created as many important changes in modern society as did the invention of alphabetical writing in antiquity and movable type in the fifteenth century. It is more than a natural phenomenon that science has harnessed for human use; it is a central feature of the modern episteme. It has inspired writers and artists, propelled industry and innovation, and reshaped human social behaviour. Looking at a variety of topics including film, politics, and contemporary art, this volume explores the impact of electricity on knowledge, social practices, media, community life, and subjective experience.,La découverte scientifique et la maîtrise de l'électricité ont bouleversé notre société au même titre que l'invention de l'écriture alphabétique durant l'Antiquité et de l'imprimerie à caractères mobiles au XVe siècle. Il ne s'agit pas seulement d'un phénomène naturel mis au service de l'homme par la science, mais d'un élément central de l'épistémè moderne : l'électricité a inspiré des écrivains et des artistes, a servi de force d'impulsion au monde de l'industrie et de l'innovation et a redéfini les comportements sociaux. En explorant l'incidence de l'électricité sur le savoir, les pratiques sociales, les médias, la vie sociale et les expériences personnelles, cet ouvrage tente d'en saisir les aspects techniques et culturels dans toute leur complexité.
Code: L'ère électrique. The Electric Age Reporter: L'ère électrique. The Electric Age Series Title: Transferts culturels | Cultural Transfers
Keywords: _CL; discovery; découverte; electricity; innovation; science; électricité

The Internationalization of Capital: The Late Nineteenth and Twentieth Centuries - Saul, Samir (Empires and Autonomy, 2010)
Chapter 6 The Internationalization of Capital: The Late Nineteenth and Twentieth Centuries was published in Empires and Autonomy on page 93.
Section: Empires and Autonomy

European Capital and its Impact on Land Distribution in Egypt: A Quantitative Analysis (1900–1914) - Saul, Samir (Colonialism and the Modern World, 2002)
Of paramount importance in the economic, social, and political history of modern Egypt has been the issue of land distribution. As the primary asset in an economy based on agriculture until the latter part of the twentieth century, land represented the livelihood of the majority of Egyptians, a source of wealth for some and a means of achieving social status for all. Ownership of land was necessary in order to benefit—directly as a cultivator or indirectly as a proprietor earning rents—from Egypt’s natural advantages as a cotton-growing country and the usually high prices it fetched on the international market. Arable land was all the more valuable in that it was rare in a territory largely made up of vast expanses of desert. The problem created by the dearth of tillable land was compounded by the rapid rise of the population.
Num Pages: 25

Les inspecteurs des finances et l'outre-mer de 1870 à 1945 - Saul, Samir (Dictionnaire historique des inspecteurs des finances, 1801-2009 dictionnaire thématique et biographique, 2012)
Section: 1 vol. (1131 p.) : ill. ; 22 cm.

Émile Minost - Saul, Samir (Dictionnaire historique des inspecteurs des finances, 1801-2009 dictionnaire thématique et biographique, 2012)
Section: 1 vol. (1131 p.) : ill. ; 22 cm.

L'électrification du Maroc à l'époque du protectorat - Saul, Samir (L'électrification outre-mer de la fin du XIXe siècle aux premières décolonisations: actes du XIIIe colloque international de l'Association pour l'histoire de l'électricité en France, Paris, les 14 et 15 juin 2000, 2002)
Section: 664 pages : illustrations, cartes ; 24 cm. Fondation EDF. Association pour l'histoire de l'électricité en France. Colloque (13 ; 2000 ; Paris). https://www.persee.fr/doc/outre_1631-0438_2002_num_89_334_3952

Le pari économique de la guerre d'Algérie - Saul, Samir (Pourquoi la France a-t-elle fait la guerre d'Algérie?, 2023)
Fondation pour la mémoire de la guerre d'Algérie, des combats du Maroc et de Tunisie Actes du colloque du 18 mars 2022 « Pourquoi la France a-t-elle fait la guerre d'Algérie? »
Keywords: 20th century; Algeria; Congresses; France; History; History; Military; Revolution; 1954-1962

Liaisons laborieuses : les relations économiques France-États-Unis depuis 1945 - Saul, Samir (Banque et société XIXe-XXIe siècle: identités croisées: hommage à Pierre de Longuemar, 2016)

Débat: Pierre Mendès France et les relations internationales - Bossuat, Gérard; Saul, Samir; Hessel, Stéphane; Kahn, Marcel-Francis; Weil, Georges; Geissman, Pierre-Maurice (Matériaux pour l'histoire de notre temps, 2001)

Les sociétés coloniales au Proche et Moyen-Orient - Saul, Samir (Les sociétés coloniales à l'âge des empires des années 1850 aux années 1950, 2012)
Section: 1 vol. (400 p.) : ill., cartes, tabl., couv. ill. ; 24 cm.

Dictionnaire historique des inspecteurs des Finances 1801-2009 Dictionnaire thématique et biographique - Achard, Pierre; Andrieu, Claire; Asselain, Jean-Charles; Baruch, Marc Olivier; Bassères, Jean; Blancheton, Bertrand; Bonin, Hubert; Bossuat, Gérard; Boudon, Jacques-Olivier; Bussière, Éric; Cahart, Patrice; Cardoni, Fabien; et al. (Institut de la gestion publique et du développement économique, 2014)